Respectable Citizens: Gender, Family, and Unemployment in Ontario's Great Depression - Campbell, Lara A. (University of Toronto Press, 2009)
High unemployment rates, humiliating relief policy, and the spectre of eviction characterized the experiences of many Ontario families in the Great Depression. Respectable Citizens is an examination of the material difficulties and survival strategies of families facing poverty and unemployment, and an analysis of how collective action and protest redefined the meanings of welfare and citizenship in the 1930s.Lara Campbell draws on diverse sources including newspapers, family and juvenile court records, premiers' papers, memoirs, and oral histories to uncover the ways in which the material workings of the family and the discursive category of 'respectable' citizenship were invested with gendered obligations and Anglo-British identity. Respectable Citizens demonstrates how women and men represented themselves as entitled to make specific claims on the state, shedding new light on the cooperative and conflicting relationships between men and women, parents and children, and citizen and state in 1930s Canada. --Publisher's description

Fight Back: Workplace Justice for Immigrants - Choudry, Aziz; Hanley, Jill; Jordan, Steve; Stiegman, Martha; Schragge, Eric (Race & Racism, 2009)
[D]ocuments the struggles of immigrant workers and analyses them within the context of neoliberal globalization and the international and national labour markets. Fight Back grew out of collaboration between a group of university-affiliated researchers who are active in different social movements and community organizations in partnership with the Immigrant Workers Centre in Montreal. The book shares with us the experiences of immigrant workers in a variety of workplaces. It is based on the underlying belief that the best kind of research that tells “how it really is” comes from the lived experience of people themselves. -- Publisher's description. Contents: Introduction -- Context -- Making immigrant workers -- Access to social rights for migrants to Canada: the long divide between the law and the real world -- Seasonal agricultural workers -- Canada's live-in caregiver program : popular among both employers and migrants, but structured for dependency and inequality -- Survival and fighting back.
Keywords: Canada; Canada. Immigrants; Conditions économiques. Immigrants; Economic conditions. Immigrants; Employment; Immigrants; Social conditions. Immigrants; Travail

Philippe Vaillancourt : militant syndical et politique - Comby, Marc (VLB, 2009)
Philippe Vaillancourt (1913-1984) est venu à l'action syndicale par la politique et, durant toute sa carrière, il a conjugué ces deux formes d'engagement. Amorcé pendant la Grande Crise pour se terminer pendant la Révolution tranquille, le parcours militant de Philippe Vaillancourt a été particulièrement ardu, en butte entre autres à l'opposition du gouvernement de Maurice Duplessis. Suivre Philippe Vaillancourt dans cette période pionnière, c'est revivre des conflits du travail souvent violents, c'est suivre l'histoire des rivalités et des regroupements de syndicats, des tentatives de ces derniers de créer un parti ouvrier en s'alliant avec la Cooperative Commonwealth Federation (CCF), puis avec le Nouveau Parti Démocratique (NPD), de T.C. Douglas. Fermement convaincu de l'importance de l'éducation syndicale, Philippe Vaillancourt a consacré à cette priorité les dernières années de sa carrière au Congrès canadien du travail (CCT) pour le Québec, dont est membre la Fédération des travailleurs du Québec (FTQ). --Résumé de l'éditeur
Keywords: Vaillancourt, Philippe, 1913-1984

Games of Empire: Global Capitalism and Video Games - Dyer-Witheford, Nick; De Peuter, Greig (Electronic mediations, 2009)
In the first decade of the twenty-first century, video games are an integral part of global media culture, rivaling Hollywood in revenue and influence. No longer confined to a subculture of adolescent males, video games today are played by adults around the world. At the same time, video games have become major sites of corporate exploitation and military recruitment. In Games of Empire, Nick Dyer-Witheford and Greig de Peuter offer a radical political critique of such video games and virtual environments as Second Life, World of Warcraft, and Grand Theft Auto, analyzing them as the exemplary m
Keywords: Capitalism Social aspects; Computerspiel; GAMES Video & Electronic; Imperialism Social aspects; Impérialisme Aspect social; Jeux vidéo Aspect social; Jeux vidéo Aspect économique; Tv-spel ekonomiska aspekter; Tv-spel sociala aspekter; Video games Economic aspects; Video games Social aspects; Wirtschaft

Unions, Equity, and the Path to Renewal - Foley, Janice R.; Baker, Patricia L. (UBC Press, 2009)
Trade unions in Canada are losing their traditional support base, and membership numbers could sink to US levels unless unions recapture their power. Unions, Equity, and the Path to Renewal brings together a distinguished group of union activists and equity scholars who trace how traditional union cultures, practices, and structures have eroded solidarity and activism and created an equity deficit in Canadian unions. Informed by a feminist vision of unions as instruments of social justice, the contributors argue that equity within unions is not simply one possible path to union renewal – it is the only way to reposition organized labour as a central institution in workers’ lives. --Publisher's description
Keywords: Canada; Equality; Labor unions; Social aspects; Women in the labor movement

The Prestige Squeeze: Occupational Prestige in Canada Since 1965 - Goyder, John (McGill-Queen's University Press, 2009)
How Canadians rate the prestige of their occupations, and what this says about our understanding of the knowledge economy, social mobility and inequality, and our working selves. "What do you do?" is often the first question posed when strangers meet, as occupation reveals a great deal about both social identity and social standing or "occupational prestige." Sociologists have studied occupational prestige for decades, including a landmark national survey in 1965 by Peter Pineo and John Porter. John Goyder updates Pineo and Porter's work, providing a detailed comparison of their results with a similar national scale survey conducted in 2005. The results challenge the accepted view that prestige ratings are constant over time and across societies. Goyder shows that there have been some surprising changes in these ratings: instead of the expected premium on jobs in the knowledge sector, more traditional occupations - such as the skilled trades, even if they require little education or pay a low wage - have gained the most prestige. There has been a significant decrease in consensus about occupational prestige ratings and the tendency for respondents to upgrade the prestige of their own occupation is much more pronounced in the recent data. Goyder argues that these changes are a sign of the shifting nature of values in a meritocratic society in which increasing income inequality is a growing reality. Results from prestige surveys help in the construction of socio-economic scales for occupations and inform career counselling for young people and negotiations by labour unions and associations. "The Prestige Squeeze" goes beyond this to question the very nature of how we measure social equality and mobility. --Publisher's description

Canadian Labour and Employment Relations - Gunderson, Morley; Taras, Daphne Gottlieb (Pearson Addison Wesley, 2009)
Contents: Canadian labour and employment relations / Daphne G. Taras and Morley Gunderson -- Understanding the unionization decision / Ann C. Frost and Daphne G. Taras -- Labour history and the development of modern capitalism / Richard Marsden -- Unions : membership, structures, actions and challenges / Gregor Murray -- The management of industrial relations / Mark Thompson -- Managing the high-involvement workplace / Anil Verma and Daphne G. Taras -- Social, political, and economic environments / Frank Reid and Rafael Gomez -- Collective bargaining legislation in Canada / Sara Slinn -- The individual employment contract and employment / Geoffrey England -- Collective bargaining : structure, process, and innovation / Richard Chaykowski -- The collective agreement / Anthony Giles and Akivah Starkman -- Strikes and dispute resolution / Morley Gunderson, Bob Hebdon, and Douglas Hyatt -- The grievance arbitration process and workplace / Kenneth Wm. Thornicroft -- Union impact on compensation, productivity, and management of the organization / Morley Gunderson and Douglas Hyatt -- Public-sector collective bargaining / Mark Thompson and Patrice Jalette -- Union-management relations in Québec / Esther Déom and Jean-Noël Grenier with Marie-Pierre Beaumont -- Trade unions and labour relations regimes: international perspectives in a globalizing world / Carla Lipsig-Mummé. Previous eds. published under title: Union-management relations in Canada; Includes bibliographical references and index.
Keywords: Industrial relations -- Canada -- Textbooks

Laying It on the Line: Driving a Hard Bargain in Challenging Times - Hargrove, Buzz (HarperCollins, 2009)
In late 2008, the world’s economy began to tumble at avalanche speed, and at the forefront of the manufacturing collapse were the Big Three automakers: Chrysler, General Motors and Ford. For decades, these companies had been shining stars, providing billions of dollars of new investments and thousands of well-paying jobs. Yet suddenly the heads of these and other manufacturing giants found themselves begging governments for financial packages to save their industries. What the hell happened? Buzz Hargrove, the former head of the Canadian Autoworkers (CAW), retired right before the collapse, but not before witnessing the decades of bad decisionmaking— by federal governments and CEOs—that set the stage for the sudden crisis. No one knows the ins and outs of manufacturing like Hargrove, a man who championed the cause of on-the-line workers but who also earned the immense respect of political and business leaders. In Laying It on the Line, Hargrove explains the crisis from his side of the table, what it means for Canada and how the manufacturing sector can again become this country’s foremost economic driver. Along the way, he shares the behind-the-door dealings with GM, Ford, Air Canada and others, explaining the controversial agreements he reached over his decades as Canada’s chief labour leader. Laying It on the Line is a timely call to arms for industry, governments and indeed all Canadians. --Publisher's description
Keywords: 20th century; 21st century; Automobile industry History; Automobile industry and trade; Canada; Collective labor agreements; Hargrove, Buzz; History; Industrial relations; Manufacturing industries

Rig: An Oral History of the Ocean Ranger Disaster - Heffernan, Mike (Creative Publishers, 2009)
In the early hours of February 15, 1982, tragedy struck the Ocean Ranger oil rig when it capsized and sank in a severe weather storm 170 nautical miles east of St. John's, Newfoundland. All of the eighty-four crewmen perished, including fifty-six men from the province. This was Canada's greatest maritime disaster since World War II. Rig is a powerful story filled with first-person accounts and previously unpublished photographs. In an intimate journey through grief and sadness, Rig searches for reconciliation among the victims' families and those who risked their own lives to help those on the Ocean Ranger. --Publisher's description
Keywords: Ocean Ranger (Drilling rig)

Canadian Maverick: The Life and Times of Ivan C. Rand - Kaplan, William (Published for the Osgoode Society for Canadian Legal History by University of Toronto Press, 2009)
Ivan Rand had a long, varied and remarkable career. He is best known for his Supreme Court of Canada judgments in a series of cases emanating from Quebec in the 1950s and dealing with civil rights, cases which established limits on the government’s ability to persecute unpopular religious minorities. To labour lawyers he is also an icon for his invention of the ‘Rand formula’, one of the defining features of Canadian labour law. Rand was also a member of the United Nations special committee on Palestine in 1947, the founding Dean of the University of Western Ontario law school, and three times a royal commissioner, looking into the problems of the Canadian coal industry, the misconduct of Mr. Justice Leo A. Landreville, and labour disputes in Ontario. In this thoroughly researched and fast-paced book, William Kaplan traces Rand’s life and career in all its richness and controversy – Rand as lawyer, politician, judge, dean, and royal commissioner – through many seminal events of the twentieth century in Canada. The Rand that emerges is variously inspiring, frustrating to understand, sometimes contradictory, always complex. --Publisher's description

Essex County: A Graphic Novel - Lemire, Jeff. (Top Shelf Productions, 2009)
Where does a young boy turn when his whole world suddenly disappears? What turns two brothers from an unstoppable team into a pair of bitterly estranged loners? How does the simple-hearted care of one middle-aged nurse reveal the scars of an entire community, and can anything heal the wounds caused by a century of deception? Award-winning cartoonist Jeff Lemire pays tribute to his roots with Essex County, an award-winning trilogy of graphic novels set in an imaginary version of his hometown, the eccentric farming community of Essex County, Ontario, Canada. In Essex County, Lemire crafts an intimate study of one community through the years, and a tender meditation on family, memory, grief, secrets, and reconciliation. With the lush, expressive inking of a young artist at the height of his powers, Lemire draws us in and sets us free. This new edition collects the complete, critically-acclaimed trilogy (Tales from the Farm, Ghost Stories, and The Country Nurse) in one deluxe volume! Also included are over 40-pages of previously unpublished material, including two new stories. This title has been voted by Canada Reads Top 10 title for the decade! --Publisher's description
Keywords: Blue-collar work; Farming community; Nurse; Ontario Essex; Sabotage

The Factory Voice - Lynes, Jeanette (Coteau Books, 2009)
Wrapped around the stories of these four women, is a mystery. Something''s gone wrong with the Mosquitos being built for the war effort -- they keep crashing in flight tests, for no apparent reason. Is the problem with their design, or are they being sabotaged? By whom? The traitorous Red Finns? The political subversives who have recently escaped from one of the nearby prison camps? Everyone''s on high alert, and "The Factory Voice" keeps abreast of the details. Or at least the rumours. --Publisher's description
Keywords: 1939-1945; Airplane factories; Airplane factories Fiction; Amitié féminine Romans, nouvelles, etc; Avions Usines Romans, nouvelles, etc; Canada; Female friendship; Female friendship Fiction; Fiction; Guerre mondiale, 1939-1945 Femmes Romans, nouvelles, etc; Historical fiction; Northern Ontario; Ontario, Northern Fiction; Women; World War, 1939-1945 Canada Fiction; World War, 1939-1945 Women Fiction

The Guy in the Green Truck: A Biography of John St. Amand - McCrorie, James Napier (Roseway/Fernwood, 2009)
Affectionate portrait of John St. Amand (1943-2007) who, under the tutelage of the left-wing labour activist, Madeleine Parent, moved in 1981 from Ontario to Nova Scotia to become a union organizer.
Keywords: History; Labor Unions; Officials and employees; Organizing; St. Amand, John, 1943-2007

Labour Pains: Thunder Bay's Working Class in Canada's Wheat Boom Era - Morrison, Jean; Thunder Bay Historical Museum Society (Thunder Bay Historical Museum Society, 2009)
Through painful struggles and changing relationships, Thunder Bay’s working class defined itself during the tumultuous years before World War I. Labour Pains looks at many responses to the harshness of industrialism: trade unionism and labour politics, unrest and violence, the Social Gospel and socialism, mediation and conciliation. Alliances and conflict, many ethnicities and various expressions of class consciousness all contributed to the making of the working class whose members and defenders embraced many remarkable individuals, known and unknown. --Publisher's description. Contents: The beginnings of Thunder Bay's working class [Thunder Bay, Northwestern Ontario] -- Trade unions, municipal ownership & labour politics : Harry Bryan and the advent of organized labour] -- Dock workers, immigrants and the railways -- Socialism, the social gospel and labour politics [labor] -- The 1909 Freight Handlers Strike -- Who won the 1909 strike? -- Labour, socialists and the 1912 Coal Handlers Strike -- The Justice system, immigrants and waterfront strikes : socialists and violence -- The 1913 Street Railwaymen's Strike -- Reformers and rebels, good deeds and discord -- Appendix A. Labour unions in Port Arthur and Fort William in 1910. Includes bibliographical references (p. 170-174) and index.
Keywords: History; Labor unions; Ontario; Strikes and lockouts; Thunder Bay, Ont.; Working class

The National Farmers Union: Working for Farm Families for 40 Years. - National Farmers Union (Canada) (National Farmers Union, 2009)
The NFU was formed in 1969 through a merger of the Saskatchewan Farmers Union, the Ontario Farmers Union, the Farmers Union of British Columbia, and the Farmers Union of Alberta. In addition to these provincial unions, farmers from the Maritime provinces—not organized into farmers’ unions at the time—also became part of the NFU structure. Prior to ’69, these provincial unions each had worked autonomously in its respective province, but increasingly they were finding themselves at a disadvantage in attempting to work with the federal government. In an effort to solve that problem, the unions created a coordinating body, the National Farmers Union Council, consisting of representatives of the executives of each provincial union and representatives from the Maritime provinces. Over time, the officials and members from the provincial unions and the Maritimes realized that the major policy decisions affecting farmers were being made at the federal level. At a joint meeting of the executives of the provincial unions and others in Winnipeg in March 1968, the executive members passed a motion to strike a committee to develop a constitution for a direct membership national farm organization. The founding convention of the National Farmers Union was held in Winnipeg in July 1969. In the following months the provincial unions were phased out and their assets and liabilities transferred to the national organization. --Publisher's description

Harvest Pilgrims: Mexican and Caribbean Migrant Farm Workers in Canada - Pietropaolo, Vincenzo (Between the Lines, 2009)
Like migratory birds, most of Canada’s 20,000 “guest” farm workers arrive in the spring and leave in the autumn. Hailing primarily from Mexico, Jamaica, and smaller countries of the Caribbean, these temporary workers have become entrenched in the Canadian labour force and are the mainstay of many traditional family farms in Canada. Many of them make the trip year after year after year.Vincenzo Pietropaolo has been photographing guest workers and recording their stories since 1984 – in the process travelling to forty locations throughout Ontario and to their homes in Mexico, Jamaica, and Montserrat. The resulting photographs have been highly acclaimed internationally through many publications and exhibitions, including a travelling show curated by the Canadian Museum of Contemporary Photography that opened in Mexico City.With a foreword by Naomi Rosenblum, this beautiful and timely book of photography and exposition aims to shed light on a subject about which many Canadians know all too little. --Publisher's description

Neighbours and Networks: The Blood Tribe in the Southern Alberta Economy, 1884-1939 - Regular, W. Keith (William Keith) (University of Calgary Press, 2009)
[E]xplores the economic relationship that existed between the Blood Indian reserve and the surrounding region of southern Alberta between 1884 and 1939. The Blood tribe, though living on a reserve, refused to become economically isolated from the larger community and indeed became significant contributors to the economy of the area. Their land base was important to the ranching industry. Their products, especially coal and hay, were sought after by settlers, and the Bloods were encouraged, not only to provide them as needed, but also to become expert freighters, transporting goods from the reserve for non-Native business people. Blood field labor in the Raymond area sugar beet fields was at times critical to the functioning of that industry. In addition, the Bloods' ties to the merchant community, especially in Cardston and Fort Macleod, resulted in a significant infusion of money into the local economy. Regular's study fills the gap left by Canadian historiography that has largely ignored the economic associations between Natives and non-Natives living in a common environment. His microhistory refutes the perception that Native reserves have played only a minor role in regional development and provides an excellent example of a cross-cultural, co-operative economic relationship in the post-treaty period on the Canadian plains. --Publisher's description. Contents: Introduction -- 'Free Range or Private Property': Integrating Blood Reserve Land into the Non-Native Economy -- 'Selling to Outsiders': Marketing Coal, Hay, and Freighting Services -- 'All the Indians Have Gone to the Beet': Blood Labour in the Raymond Sugar Beet Fields -- 'A Prospective Citizen of No Mean Importance': The Bloods and the Business Community -- Conclusion: Change Over Time.
Keywords: Alberta; Blood Indian Reserve No. 148 (Alta.); Commerce; Economic conditions; History; Indian business enterprises; Kainah Indians

Regulating Flexibility: The Political Economy of Employment Standards - Thomas, Mark P. (McGill-Queen's University Press, 2009)
In a contemporary labour market that includes growing levels of precarious employment, the regulation of minimum employment standards is intricately connected to conditions of economic security. With a focus on the role of neoliberal labour market policies in promoting "flexible" employment standards legislation - particularly in the areas of minimum wages and working time - Mark Thomas argues that shifts toward "flexible" legislation have played a central role in producing patterns of labour market inequality. Using an analytic framework that situates employment standards within the context of the broader social relations that shape processes of labour market regulation, Thomas constructs a case study of employment standards legislation in Ontario from 1884 to 2004. Drawing from political economy scholarship, and using a qualitative research methodology, he analyses class, race, and gender dimensions of legislative developments, highlighting the ways in which shifts towards "flexible" employment standards have exacerbated longstanding racialized and gendered inequities. Regulating Flexibility argues that in order to counter current trends towards increased insecurity, employment standards should not be treated as a secondary form of labour protection but as a cornerstone in a progressive project of labour market re-regulation. --Publisher's description

Gender and the Contours of Precarious Employment - Vosko, Leah F.; MacDonald, Martha; Campbell, Iain (Routledge IAFFE advances in feminist economics, 2009)
Precarious employment presents a monumental challenge to the social, economic, and political stability of labour markets in industrialized societies and there is widespread consensus that its growth is contributing to a series of common social inequalities, especially along the lines of gender and citizenship. The editors argue that these inequalities are evident at the national level across industrialized countries, as well as at the regional level within federal societies, such as Canada, Germany, the United States, and Australia and in the European Union. This book brings together contributions addressing this issue which include case studies exploring the size, nature, and dynamics of precarious employment in different industrialized countries and chapters examining conceptual and methodological challenges in the study of precarious employment in comparative perspective. The collection aims to yield new ways of understanding, conceptualizing, measuring, and responding, via public policy and other means - such as new forms of union organization and community organizing at multiple scales - to the forces driving labour market insecurity. --Publisher's description
Keywords: Alemania; Allemagne; Analyse comparative; Arbeitsmarkt; Arbetsmarknad genusaspekter; Australia; Australie; Canada; Canadá; Contract system (Labor); Espagne; España; Estados Unidos; Etats-Unis; Etats-Unis d'Amérique; Fackligt arbete; France; Francia; Frau; Genre; Germany; Inégalités sociales; Ireland; Irlanda; Irlande; Japan; Japon; Japón; Marché du travail; Netherlands; Niedriglohn; Pays développés; Pays-Bas; Países Bajos; Precarious employment; Précarité; Reino Unido de Gran Bretaña e Irlanda del Norte; Royaume-Uni de Grande-Bretagne et d'Irlande du Nord; Rörlighet på arbetsmarknaden; Sexual division of labor; Spain; Suecia; Suède; Sweden; Temporary employment; Travail précaire; Travail temporaire; UE/CE Etats membres; USA; United Kingdom of Great Britain and Northern Ireland; Women Employment; Zeitarbeit; chômage; desempleo; division du travail basée sur le sexe; división del trabajo por sexo; empleo a tiempo parcial; empleo precario; empleo temporal; emploi précaire; emploi temporaire; emploi à temps partiel; men workers; part time employment; precarious employment; sexual division of labour; temporary employment; trabajadoras; trabajadores masculinos; travailleurs masculins; travailleuses; unemployment; women workers

If You're in My Way, I'm Walking: The Assault on Working People since 1970 - Workman, W. Thom (Fernwood Pub., 2009)
“If you’re in my way I’m walking.” This arrogant statement by former Prime Minister Jean Chrétien on the occasion of his physical altercation with a protester in Hull, Quebec in the mid-1990s symbolizes the spirit of the relentless drive of capital to rewrite the historical compromise reached with working people after World War II. This early post-war compromise—sometimes referred to as the Fordist Compact—was associated with improving wages and rising living standards for working people. But in recent decades those achievements of the working class are being deliberately rolled back. Workman surveys many features of this experience: changing public perceptions of working life, the deregulation of labour law, the decline in unionization rates, the eclipse of union militancy, the stagnation of real wages, the disproportionate absorption of women into the low-wage sphere and the dismantling of social policy. He demonstrates the unravelling of the post-war compact and its replacement with a far more ex-ploitative relationship between capital and labour. He also points to the decline of the Canadian left and its inability to counter the capitalist onslaught effectively. Nevertheless, there are reasons to be hopeful. Workman calls for a rebuilding of the left through the restoration of left culture. To do this he says that the left must “quit politics,” work to promote the collective memory of working-class achievements, create venues to listen to working people in today’s economy, reject nationalism outright and encourage the labour movement to exploit its disruptive capacity. This revitalized left will form the basis of a deepening social critique, the political lessons of which will prove to be invaluable for working people in the long run. -- Publisher's description
Keywords: Labor Unions; Labor movement; Neoliberalism; Right and left (Political science); Working class

Political Trials and Security Measures, 1840-1914 - Wright, Barry; Binny, Susan (Canadian State Trials, 2009)
This third volume of the Osgoode Society’s Canadian State Trials series covers the period from the 1840s to the First World War. It examines a range of political trials as traditionally defined, including those arising from the Fenian invasions and the North-West Rebellions. The volume also expands the definition of state trials to include studies on the early development of secret policing and the evolution of the legal regulation of riot and public order. The editors have assembled a team of experts from across the country in a variety of fields, and produced a comprehensive and fascinating set of studies of the use of law to control political dissent and public disorder.--Publisher's description.
Keywords: Political crimes and offenses -- Canada -- History

Why Unions Matter - Yates, Michael (Monthly Review Press, 2009)
In this new edition the author shows why unions still matter. Unions mean better pay, benefits, and working conditions for their members; they force employers to treat employees with dignity and respect; and at their best, they provide a way for workers to make society both more democratic and egalitarian. The author uses both data, and examples to show why workers need unions, how unions are formed, how they operate, how collective bargaining works, the role of unions in politics, and what unions have done to bring workers together across the divides of race, gender, religion, and sexual orientation. The new edition not only updates the first, but also examines the record of the New Voice slate that took control of the AFL-CIO in 1995, the continuing decline in union membership and density, the Change to Win split in 2005, the growing importance of immigrant workers, the rise of worker centers, the impacts of and labor responses to globalization, and the need for labor to have an independent political voice, and the Employee Free Choice Act. --Publisher's description
Keywords: Labor unions; Labor unions United States; United States

Selling Diversity: Immigration, Multiculturalism and Employment Equity - Abu-Laban, Yasmeen; Gabriel, Christina (Broadview Press, 2008)
Since the 1990s, Canadian policy prescriptions for immigration, multiculturalism, and employment equity have equated globalization with global markets. This interpretation has transformed men and women of various ethnic backgrounds into trade-enhancing commodities who must justify their skills and talents in the language of business. This particular neo-liberal reading of globalization and public policy has resulted in a trend the authors call selling diversity. Using gender, race/ethnicity, and class lenses to frame their analysis, the authors review Canadian immigration, multiculturalism, and employment equity policies, including their different historical origins, to illustrate how a preference for selling diversity has emerged in the last decade. In the process they suggest that a commitment to enhance justice in a diverse society and world has been muted. Yet, neo-liberalism is not the only or inevitable option in this era of globalization, and Canadians are engaging in transnational struggles for rights and equality and thereby increasing the interconnectedness between peoples across the globe. Consequently, the emphasis on selling diversity might be challenged.
Keywords: Diversity; Equality; Equity; Immigrants

Building a Better World: An Introduction to Trade Unionism in Canada - Black, Errol; Silver, James (Fernwood, 2008)
Substantially revised and updated, this widely used introductory text emphasizes how values, objectives and activities of unions are shaped in the face of employer resistance and hostile governments. It includes an analysis of why workers form unions; organization and democracy; collective bargaining and grievances; historical development; and gains unions have achieved for their members and all working people. It also examines the challenges created by rapid economic and technological change, the rise of neoliberalism and the increasingly contingent and acialized character of the labour force. --Publisher's description
Keywords: History; Labor Unions

Nation and Society: Readings in Post-Confederation Canadian History, volume 2 - Conrad, Margaret; Finkel, Alvin (Pearson Longman, 2008)
[This textbook] is a balanced collection of the best readings on the history of Canada since Confederation. The readings are separated into five parts: Inventing Canada, 1867-1914; Economy and society in the Industrial Age, 1867-1918; Transitional years, Canada 1919-1945; Reinventing Canada, 1945-1975; and Post-Modern Canada. With 13 new readings, the book will challenge and enlighten students by opening a window to Canada's past and to the ever-evolving examination of Canadian history. --Publisher's description
Keywords: Canada -- History -- 1867- -- Textbooks

Barnacle Love - De Sa, Anthony (Penguin Random House Canada, 2008)
Like Wayson Choy and David Bezmozgis before him, Anthony De Sa captures, in stories brimming with life, the innocent dreams and bitter disappointments of the immigrant experience. At the heart of this collection of intimately linked stories is the relationship between a father and his son. A young fisherman washes up nearly dead on the shores of Newfoundland. It is Manuel Rebelo who has tried to escape the suffocating smallness of his Portuguese village and the crushing weight of his mother’s expectations to build a future for himself in a terra nova. Manuel struggles to shed the traditions of a village frozen in time and to silence the brutal voice of Maria Theresa da Conceicao Rebelo, but embracing the promise of his adopted land is not as simple as he had hoped. Manuel’s son, Antonio, is born into Toronto’s little Portugal, a world of colourful houses and labyrinthine back alleys. In the Rebelo home the Church looms large, men and women inhabit sharply divided space, pigs are slaughtered in the garage, and a family lives in the shadow cast by a father’s failures. Most days Antonio and his friends take to their bikes, pushing the boundaries of their neighbourhood street by street, but when they finally break through to the city beyond they confront dangers of a new sort. With fantastic detail, larger-than-life characters and passionate empathy, Anthony De Sa invites readers into the lives of the Rebelos and finds there both the promise and the disappointment inherent in the choices made by the father and the expectations placed on the son. --Publisher's description
Keywords: Authors, Canadian (English) 21st century; Canadian fiction; Domestic fiction; Fiction; Immigrants; Immigrants Fiction; Newfoundland and Labrador; Newfoundland and Labrador Fiction; Nouvelles; Ontario Toronto; Short stories; Toronto (Ont.) Fiction; short stories

Cultivating Farmworker Rights: Ending the Exploitation of Immigrant and Migrant Farmworkers in BC - Fairey, David; Hanson, Christina; MacInnes, Glen; McLaren, Arlene Tigar; Otero, Gerardo; Thompson, Mark (Canadian Centre for Policy Alternatives, 2008)
A new study of farm work in BC reveals systematic violations of employment standards and health and safety regulations, poor and often dangerous working conditions, and dismal enforcement by government agencies. The study’s authors propose comprehensive policy changes that would ensure farmworkers — most of whom are immigrants and temporary migrants — are no longer relegated to second-class status. “Farmworkers are at the mercy of a complex and confusing system that exploits, threatens and silences them while putting their lives in danger,” says study co-author Arlene McLaren, Professor Emerita of Sociology at Simon Fraser University. The study draws from numerous sources, including interviews with key informants in government and the farm industry, interviews with 53 Indo-Canadian immigrant and Mexican migrant farmworkers, a survey 87 Mexican migrant farmworkers, and a review of better practices in other jurisdictions. The study is part of the Economic Security Project, a joint initiative of the Canadian Centre for Policy Alternatives and Simon Fraser University. --Publisher's description
Keywords: Agricultural laborers; British Columbia; Civil rights; Legal status, laws, etc

Industrial Relations in Canada - Hebdon, Robert; Brown, Travor C. (Nelson Series in Human Resources Management, 2008)
This text presents a hands-on examination of industrial relations balanced in both theoretical and practical coverage, as well as union and labour coverage. Industrial Relations in Canada is grounded in leading research and examines true-to-life issues. Experiential exercises, cases, and collective bargaining simulations bridge the academic content of the text with real-world issues in the field. --Publisher's description of 2011 edition.

Working in Steel: The Early Years in Canada, 1883-1935 - Heron, Craig (Canadian social history series, 2008)
In this indispensable study of Canadian industrialization, Craig Heron examines the huge steel plants that were built at the turn of the twentieth century in Sydney and New Glasgow, Nova Scotia, and Trenton, Hamilton, and Sault Ste. Marie, Ontario. Presenting a stimulating analysis of the Canadian working class in the early twentieth century, Working in Steel emphasizes the importance of changes in the work world for the larger patterns of working-class life. Heron's examination of the impact of new technology in Canada's Second Industrial Revolution challenges the popular notion that mass-production workers lost all skill, power, and pride in the work process. He shifts the explanation of managerial control in these plants from machines to the blunt authoritarianism and shrewd paternalism of corporate management. His discussion of Canada's first steelworkers illuminates the uneven, unpredictable, and conflict-ridden process of technological change in industrial capitalist society. As engaging today as when first published in 1988, Working in Steel remains an essential work in Canadian history. --Pubisher's description
Keywords: Canada; Capitalism; History; Industrial; Working class

One Step Over the Line: Toward a History of Women in the North American Wests - Jameson, Elizabeth; McManus, Sheila (West unbound, 2008)
This eclectic and carefully organized range of essays--from women's history and settler societies to colonialism and borderlands studies--is the first collection of comparative and transnational work on women in the Canadian and U.S. Wests. It explores, expands, and advances the aspects of women's history that cross national borders. Out of the talks presented at the 2002 "Unsettled Pasts: Reconceiving the West through Women's History," Elizabeth Jameson and Sheila McManus have edited a foundational text with a wide, inclusive perspective on our western past. --Publisher's description. Contents: Connecting the women's Wests / Elizabeth Jameson -- Unsettled pasts, unsettling borders: women, Wests, nations / Sheila McManus -- Making connections: gender, race and place in Oregon contry / Susan Armitage -- A transborder family in the Pacific North West: reflecting on race and gender in women's history / Sylvia van Kirk -- Writing women into the history of the North American Wests, one woman at a time / Jean Barman -- "That understanding with nature":region, race, and nation in women's stories from the modern Canadian and American Grasslands West / Molly P. Rozum -- The perils of rural women's history: (a note to storytellers who study the West's unsettled past) / Joan M. Jensen -- The great white mother: maternalism and American Indian child removal in the American West, 1880-1940 / Margaret D. Jacobs -- Pushing physical, racial, and ethnic boundaries: Edith Lucas and public education in British Columbia, 1903-1989 / Helen Raptis -- "Crossing the line": American prostitutes in Western Canada, 1895-1925 / Char Smith -- "Talented and charming strangers from across the line": gendered nationalism. class privilege, and the American woman's club of Calgary / Nora Faires -- Excerpts from Pourin' Down Rain / Cheryl Foggo -- "A union without women is only half organized": Mine Mill, women's auxiliaries, and cold war politics in the North American Wests / Laurie Mercier -- Jailed heroes and kithen heroines: class, gender, and the Medalta Potteries strike in postwar Alberta / Cynthia Loch-Drake -- Gendered steps across the border: teaching the history of women in the American and Canadian Wests / Margaret Walsh -- Latitudes and longitudes: teaching the history of women in the U.S. and Canadian Wests / Mary Murphy.
Keywords: Boundaries; Canada; Canada Boundaries United States; Canada Boundaries United States Congresses; Canada Frontières États-Unis; Canada Frontières États-Unis Congrès; Conference papers and proceedings; Femmes Canada (Ouest) Histoire Congrès; Femmes États-Unis (Ouest) Histoire Congrès; HISTORY General; History; United States; United States Boundaries Canada; United States Boundaries Canada Congresses; West United States; Western Canada; Women; Women Canada, Western History; Women Canada, Western History Congresses; Women West (U.S.) History; Women West (U.S.) History Congresses; États-Unis Frontières Canada; États-Unis Frontières Canada Congrès

Management of Occupational Health and Safety - Kelloway, E. Kevin; Francis, Lori D (Thomson Nelson, 2008)
Based on the premise that occupational health and safety concerns can directly impact an organizations productivity and profitability, this 4th Canadian edition of Management of Occupational Health and Safety helps Human Resource Managers understand health and safety issues, legislation and programs. This edition also provides an up-to-date review of current issues, and methodologies affecting the occupational health and safety standards and practices of Canadian organizations. --Publisher's description
Keywords: Canada; Health and Safety

Mining Town Crisis: Globalization, Labour, and Resistance in Sudbury - Leadbeater, David (Fernwood, 2008)
Sudbury is the largest hardrock mining centre in North America and among the largest in the world. Given the enormous mineral wealth that exists in the Sudbury Basin, one might think that prosperity would abound and that cultural, educational, health and social-welfare institutions would be of the highest order, existing within a well-maintained and attractive physical infrastructure. But this is not the Sudbury that people know. This book explores key aspects of Sudbury’s economic, health and social conditions. It analyzes how globalization and corporate power in a hinterland mining town have impacted on working people, how and why resistance has emerged and why alternative directions are needed. While Sudbury is the focus of this book, the Sudbury experience offers important lessons for other mining and resource communities. --Publisher's description.
Keywords: History / Canada / General; Political Science / Globalization; Political Science / Labor & Industrial Relations

Makúk: A New History of Aboriginal-White Relations - Lutz, John S. (UBC Press, 2008)
The history of Aboriginal-settler interactions in Canada continues to haunt the national imagination. Despite billions of dollars spent on the "Indian problem," Aboriginal people remain the poorest in the country. Because the stereotype of the "lazy Indian" is never far from the surface, many Canadians wonder if the problem lay with "Indians" themselves. John Lutz traces Aboriginal people's involvement in the new economy, and their displacement from it, from the first arrival of Europeans to the 1970s. Drawing upon oral histories, manuscripts, newspaper accounts, biographies, and statistical analysis, Lutz shows that Aboriginal people flocked to the workforce and prospered in the late 19th century. The roots of today's wide-spread unemployment and "welfare dependency" date only from the 1950s, when deliberate and inadvertent policy choices--what Lutz terms the "white problem"--drove Aboriginal people out of the capitalist, wage, and subsistence economies, offering them welfare as "compensation." -- Publisher's description. Contents: Introduction: Molasses stick legs -- Pomo Wawa: the other jargon -- Making the lazy Indian -- The Lekwungen -- The Tsilhqot'in -- Outside history: labourers of the aboriginal province -- The white problem -- Prestige to welfare: remaking the moditional economy -- Conclusion: the outer edge of probability, 1970-2007 -- Postscript: subordination without subjugation.
Keywords: British Columbia; Commerce; Commerce. Indians of North America; Economic conditions. Indians of North America; Employment; Employment. Indians of North America; Government relations. Indians of North America; Government relations. Whites; History. Indians of North America; Whites

Reasoning Otherwise: Leftists and the People's Enlightenment in Canada, 1890-1920 - McKay, Ian (Between the Lines, 2008)
In Reasoning Otherwise, author Ian McKay returns to the concepts and methods of 'reconnaissance' first outlined in Rebels, Reds, Radicals to examine the people and events that led to the rise of the left in Canada from 1890 to 1920. Reasoning Otherwise highlights how a new way of looking at the world based on theories of evolution transformed struggles around class, religion, gender, and race, and culminates in a new interpretation of the Winnipeg General Strike of 1919. As McKay demonstrated in Rebels, Reds, Radicals, the Canadian left is alive and flourishing, and has shaped the Canadian experience in subtle and powerful ways. Reasoning Otherwise continues this tradition of offering important new insight into the deep roots of leftism in Canada. --Publisher's description
Keywords: History; Politics and government; Right and left (Political science); Socialism

Working Girls in the West: Representations of Wage-Earning Women - McMaster, Lindsey (UBC Press, 2008)
As the twentieth century got underway in Canada, young women who entered the paid workforce became the focus of intense public debate. Young wage-earning women - "working girls"--Embodied all that was unnerving and unnatural about modern times: the disintegration of the family, the independence of women, and the unwholesomeness of city life. These anxieties were amplified in the West. Long after eastern Canada was considered settled and urbanized, the West continued to be represented as a frontier where the idea of the region as a society in the making added resonance to the idea of the working girl as social pioneer." "Using an interpretive approach that centres on literary representation, Lindsey McMaster takes a fresh look at the working heroine of western Canadian literature alongside social documents and newspaper accounts of her real-life counterparts. Working Girls in the West heightens our understanding of a figure that fired the imagination of writers and observers at the turn of the last century." --Publisher's description. Contents: Working women in the west at the turn of the century --The urban working girl in turn-of-the-century Canadian literature -- White slaves, prostitutes, and delinquents -- Girls on strike -- White working girls and the mixed-race workplace -- Conclusion: Just girls.

The Impossibilists: A Brief Profile of the Socialist Party of Canada - Newell, Peter E. (Athena, 2008)
Formed in January 1905, the Socialist Party of Canada's anti- reformist, anti-statist revolutionary platform led to ideological disputes with rival socialist groups and even arguments within the Party itself over what it stood for. Peter E Newell's absorbing and thorough account of the life and times of the Socialist Party of Canada charts the Party's pre-history in the 1890s, when the availability of translations of the works of Marx and Engels fuelled the radicalism of such figures as Daniel De Leon. It also covers the early years of the twentieth century when, with the merger of like-minded Provincial socialist parties, the SPC was founded. In the present day the party remains a beacon for socialists worldwide for its refusal to compromise its passions and beliefs. --Publisher's description
Keywords: Socialist Party of Canada

Solidarity First: Canadian Workers and Social Cohesion - O'Brien, Robert (UBC Press, 2008)
As working people’s lives become increasingly fragmented, competitive, and unequal, debates about social cohesion capture the unease of contemporary society over growing economic restructuring. Solidarity First examines the concept and practice of social cohesion in terms of its impact on, and significance for, workers in Canada. Contributors examine how social cohesion functions on multiple levels. They challenge standard approaches by highlighting the experiences of women and non-Canadians. They investigate attempts by Toyota and Magna to construct corporate forms of cohesion and efforts by a local community to forge cohesion via the new cultural economy. And they explore the relationship between cohesion in Canada and the international environment. Critically examining the issue from the ground up, Solidarity First concludes that reinvigorated worker solidarity is a prerequisite to a more worker-friendly form of social cohesion. It will be of interest to students and scholars in the fields of public policy, political science, sociology, and labour studies. --Publisher's description
Keywords: Economic conditions; Employees; Social conditions; Social integration; Social participation; Social values; Solidarity; Working class

Labouring Canada: Class, Gender, and Race in Canadian Working-Class History - Palmer, Bryan D.; Sangster, Joan (Oxford University Press, 2008)
This text is a collection of classic and contemporary articles exploring the nature of work in Canadian history from the late eighteenth century to the current day. Class relations and labour form the core of the volume, but attention will also be paid to the state and its relations with workers both formal and informal. The volume is designed as a core text for classes in Canadian labour/working-class history, taught out of history and labour studies departments. --Publisher's description
Keywords: Canada; History; Labor movement; Social history; Working class

Citizen Docker: Making a New Deal on the Vancouver Waterfront, 1919-1939 - Parnaby, Andrew (Canadian social history series, 2008)
After the First World War, many Canadians were concerned with the possibility of national regeneration. Progressive-minded politicians, academics, church leaders, and social reformers turned increasingly to the state for solutions. Yet, as significant as the state was in articulating and instituting a new morality, outside actors such as employers were active in pursuing reform agendas as well, taking aim at the welfare of the family, citizen, and nation. Citizen Docker considers this trend, focusing on the Vancouver waterfront as a case in point.After the war, waterfront employers embarked on an ambitious program - welfare capitalism - to ease industrial relations, increase the efficiency of the port, and, ultimately, recondition longshoremen themselves. Andrew Parnaby considers these reforms as a microcosm of the process of accommodation between labour and capital that affected Canadian society as a whole in the 1920s and 1930s. By creating a new sense of entitlement among waterfront workers, one that could not be satisfied by employers during the Great Depression, welfare capitalism played an important role in the cultural transformation that took place after the Second World War.Encompassing labour and gender history, aboriginal studies, and the study of state formation, Citizen Docker examines the deep shift in the aspirations of working people, and the implications that shift had on Canadian society in the interwar years and beyond. --Publisher's description. Contents: Introduction: "A good citizen policy" -- Welfare capitalism on the waterfront -- Securing a square deal -- "The best men that ever worked the lumber" -- Heavy lifting -- "From the fury of democracy, good Lord, deliver us!" -- Conclusion: from square deal to new deal. Includes bibliographical references (pages 221-234) and index.

The Dirt: Industrial Disease and Conflict at St. Lawrence, Newfoundland - Rennie, Rick (Fernwood, 2008)
In the cemeteries of St. Lawrence and several neighbouring towns on the south coast of Newfoundland lie the remains of some 200 workers, killed by the dust and radiation that permeated the area’s fluorspar mines. The Dirt chronicles the many forces that created this disaster and shaped the response to it, including the classic ‘jobs or health’ dilemma, the contentious process of determining the nature and extent of industrial disease and the desire of employers to ‘externalize’ the costs of production onto workers and communities. Central to the account is the persistent effort by workers, women in the community and other activists to gain recognition of health hazards in the mines, their effects on workers and to obtain adequate compensation for victims and their families. --Publisher's description.  Contents: Origins of a disaster: working conditions and labour relations in the 1930s -- Protest and retreat: the war years -- Industry revival, increasing hazards and the recognition of sislicosis, 1946-1956 -- More deadly perils: radiation and cancer -- "The truly ghastly total" and the lack of compensation coverage -- Mounting protest, industry closure, and the legacy of the past.
Keywords: Aspect sanitaire; Diseases; Employees; Employees Diseases; Employees Health and hygiene; Fluorspar industry; Health and hygiene; Health and hygiene. Mining; Health aspects; Industrie; Maladies; Mineral dusts; Miners; Newfoundland and Labrador; Newfoundland and Labrador St. Lawrence; Newfoundland and Labrador. Calcium Fluoride; Newfoundland and Labrador. Occupational Diseases; Newfoundland and Labrador. Silicosis; Personnel; St. Lawrence. Fluorite; St. Lawrence. Fluorspar industry; St. Lawrence. Mineral dusts; St. Lawrence. Miners; St. Lawrence. Mineurs; Terre-Neuve-et-Labrador; Toxicologie; Toxicology; Toxicology. Miners

Fighting for Justice and Dignity: The Homer Seguin Story: An Autobiography - Seguin, Homer (Journal Printing, 2008)
Self-published memoir of the Sudbury union activist, Homer Seguin (1934-2013), who championed workplace health and safety to reduce injuries and occupational diseases at mines and other industrial sites. Describes his experiences as a negotiator, president of Local 6500 of the United Steelworkers, and as a USW representative at Elliot Lake, Ontario. Also chronicles the rise of the labour movement in Sudbury and the bitter inter-union battle in the early 1960s between Mine Mill Local 598 and the Steelworkers over the right to represent 20,000 Inco workers.
Keywords: 20th century; Elliot Lake; History. Industrial relations; History. Trade-unions; International Union of Mine, Mill and Smelter Workers. Local 598; Miners; Northeastern Ontario; Occupational health and safety; Seguin, Homer; Sudbury; United Steelworkers of America. Local 6500

Canada's Jews: A People's Journey - Tulchinsky, Gerald J. J (University of Toronto Press, 2008)
The history of the Jewish community in Canada says as much about the development of the nation as it does about the Jewish people. Spurred on by upheavals in Eastern Europe in the late-eighteenth and early-nineteenth centuries, many Jews immigrated to the Dominion of Canada, which was then considered little more than a British satellite state. Over the ensuing decades, as the Canadian Jewish identity was forged, Canada underwent the transformative experience of separating from Britain and distinguishing itself from the United States. In this light, the Canadian Jewish identity was formulated within the parameters of the emerging Canadian national personality." "Canada's Jews is an account of this remarkable story as told by one of the leading authors and historians on the Jewish legacy in Canada. Drawing on his previous work on the subject, Gerald Tulchinsky describes the struggle against antisemitism and the search for a livelihood among the Jewish community. He demonstrates that, far from being a fragment of the Old World, Canadian Jewry grew from a tiny group of transplanted Europeans to a fully articulated, diversified, and dynamic national group that defined itself as Canadian while expressing itself in the varied political and social contexts of the Dominion. --Publisher's description

Détérioration des salaires des nouveaux immigrants au Québec par rapport à l'Ontario et à la Colombie-Britannique - Boudarbat, Brahim; Boulet, Maude (Choices (Institute for Research on Public Policy), 2007)
Notre étude a un double objectif. Elle vise d’abord à comparer l’évolution des salaires d’entrée des immigrants au Québec par rapport à l’Ontario et à la Colombie-Britannique. Ensemble, ces trois provinces ont accueilli 89,5 % des immigrants arrivés au Canada au cours des années 1990 (Statistique Canada 2003). Ensuite, notre analyse s’emploie à expliquer les changements observés à cet égard dans chacune des trois provinces en considérant notamment le rôle des trois facteurs relevés dans la littérature, à savoir la région d’origine et les compétences linguistiques, le rendement de l’expérience acquise à l’étranger et le cycle économique. -- Introduction
Keywords: British Columbia; British Columbia. Immigrants; Economic conditions. Immigrants; Economic conditions. Wages; Foreign workers; Ontario; Ontario. Wages; Wages

La pendaison d'Angélique : l'histoire de l'esclavage au Canada et de l'incendie de Montréal - Cooper, Afua (Éditions de l'Homme, 2007)
Dans la soirée du samedi 10 avril 1734, Montréal brûle. L'esclave Marie-Joseph- Angélique est traduite devant la justice et accusée d'avoir mis le feu. Soumise à la question extraordinaire, forme de torture atroce pendant laquelle on brise les os des jambes, elle craque et avoue avoir commis cet incendie criminel. Puis, elle est pendue. Angélique entre dans l'histoire canadienne en tant que criminelle. Cependant, son procès nous offre une occasion unique de raconter sa vie d'esclave, une vie dont on n'aurait pas entendu parler autrement. Afua Cooper fait revivre brillamment un chapitre méconnu de l'histoire du Canada, celui d'une Noire rebelle d'origine portugaise qui a cherché à briser ses chaînes. En nous présentant le vécu de cette jeune femme, elle met en lumière ce qui l'a sans doute poussée à commettre pareil crime. Par le fait même, elle détruit le mythe d'un Canada considéré comme un paradis pour les Noirs ayant échappé à l'esclavagisme des États-Unis. L'histoire d'Angélique est le plus ancien récit à propos de l'esclavage dans le Nouveau Monde. En lui consacrant cet ouvrage, Afua Cooper apporte une importante contribution à l'historiographie canadienne et met en perspective l'esclavage accepté légalement et culturellement au Canada. --Publisher's description
Keywords: Marie-Joseph-Angélique

Collective Bargaining in Canada: Human Right or Canadian Illusion? - Fudge, Derek (Fernwood, 2007)
Recounting the cuts to freedom of association and the collective bargaining process across Canada since the 1980s, this study challenges the notion that Canada is an international champion of human rights. With documentation on the assaults to the rights of Canadian workers, this text considers the ways governments intervene to stop the collective bargaining process and evaluates topics such as the history of collective bargaining in Canada, the role of the International Labor Office, and the future hope of restoring rights and fairness to labor laws. --Publisher's description
Keywords: Collective bargaining; Labor laws and legislation

Organizing the Transnational: Labour, Politics, and Social Change - Goldring, Luin; Krishnamurti, Sailaja (UBC Press, 2007)
Growing recognition of transnational practices and identities is changing the way scholars and activists ask questions about migration. Organizing the Transnational articulates a multi-level cultural politics of transnationalism to frame contemporary analyses of immigration and diasporas. With chapters by academics and activists working from diverse perspectives, the volume moves beyond the conventional focus on states and migrants to consider a wide array of institutions, actors, and forms of mobilization that shape transnational engagements and communities. Its unique approach will inform the work of researchers, practitioners, and activists interested in the dynamics of transnational social spaces. --Publisher's description
Keywords: Asians; Asians Canada; Asiatiques Canada; Asien; Canada; Changement social Canada; Community organization; Community organization Canada; Einwanderung; Ethnicity; Ethnicity Canada; Ethnicité Canada; Etnicitet Kanada; Hispanos; Immigrants; Immigrants Canada; Immigration Kanada; Kanada; Latin Americans; Latin Americans Canada; Latino-Américains Canada; Organisation communautaire Canada; Social change; Social change Canada; Social förändring Kanada; Sozialer Wandel; Transnationale Politik; Transnationalism; Transnationalisme

Guarding the Gates: The Canadian Labour Movement and Immigration, 1872-1934 - Goutor, David (UBC Press, 2007)
From the 1870s until the Great Depression, immigration was often the question of the hour in Canada. Politicians, the media, and an array of interest groups viewed it as essential to nation building, developing the economy, and shaping Canada’s social and cultural character. One of the groups most determined to influence public debate and government policy on the issue was organized labour, and unionists were often relentless critics of immigrant recruitment. Guarding the Gates is the first detailed study of Canadian labour leaders’ approach to immigration, a key battleground in struggles between different political factions within the labour movement. --Publisher's description
Keywords: Emigration and immigration; Employment; Government policy; History; Immigrants; Labor Unions; Race discrimination

Capital and Labour in the British Columbia Forest Industry, 1934-74 - Hak, Gordon H. (Gordon Hugh) (UBC Press, 2007)
The history of British Columbia’s economy in the twentieth century is inextricably bound to the development of the forest industry. In this comprehensive study, Gordon Hak approaches the forest industry from the perspectives of workers and employers, examining the two main sets of institutions that structured the relationship during the Fordist era: the companies and the unions. Drawing on theories of the labour process, Fordism, and discursive subjectivity, Hak relates daily routines of production and profit-making to broader forces of unionism, business ideology, ecological protest, technological change, and corporate concentration. The struggle of the small-business sector to survive in the face of corporate growth, the history of the industry on the Coast and in the Interior, the transformations in capital-labour relations during the period, government forest policy, and the forest industry’s encounter with the emerging environmental movement are all considered in this eloquent analysis. With its critical historical perspective, Capital and Labour in the British Columbia Forest Industry will be essential reading for anyone interested in the business, natural resource, political, social, and labour history of the province. --Publisher's description
Keywords: Forests and forestry -- British Columbia -- History

Race, Racialization, and Antiracism in Canada and Beyond - Johnson, Genevieve Fuji; Enomoto, Randy; Canadian Ethnocultural Council; National Association of Japanese Canadians; End Racism! Activism for the 21st Century Conference (2000 : Vancouver, BC) (University of Toronto Press, 2007)
This multidisciplinary volume brings together scholars and activists to examine expressions of racism in contemporary policy areas, including education, labour, immigration, media, and urban planning. While anti-racist struggles during the twentieth century were largely pitched against overt forms of racism (e.g., pogroms, genocide, segregation, apartheid, and 'ethnic cleansing'), it has become increasingly apparent that there are other, less visible, forms of racism. These subtler incarnations are of special interest to the contributors. The intent of Race, Racialization, and Antiracism in Canada and Beyond is to probe systemic forms of racism, as well as to suggest strategies for addressing them. The collection is organized by themes pertinent to political and social expressions of racism in Canada and the wider world, such as the state and its mediation of race, education and the perpetuation of racist marginalization, and the role of the media. The contributors argue that, in order to effectively combat racism, various methodological approaches are required, approaches that are reflective of the diversity of the world we seek to understand. -- Publisher's description. Contents: Introduction / Audrey Kobayashi and Genevieve Fuji Johnson -- Negotiating school: marginalized students' participation in their education process / Carl E. James -- Multicultural education: teacher candidates speak out / Donatille Mujawamariya -- The sky didn't fall: organizing to combat racism in the workplace -- the case of the alliance for employment equity / Abigail B. Bakan and Audrey Kobayashi -- Employment conditions of racial minorities in Canada: how bad is the problem of discrimination? / Mohammed A. Al-Waqfi and Harish C. Jain -- Immigrant women's activism: the past thirty-five years / Tania Das Gupta -- Critical discourse analysis: a powerful but flawed tool? / Frances Henry and Carol Tator -- Special plus and special negative: the conflict between perceptions and applications of 'special status' in Canada / Howard Ramos -- Who belongs? Expoloring race and racialization in Canada / Leanne Taylor, Carl E. James, and Roger Saul -- The racialization of space: producng surrey / Gurpreet Singh Johal -- Raceless states / David Theo Goldberg -- Multi-identifications and transformations: reaching beyond racial and ethnic reductionisms / Philomena Essed.
Keywords: Canada; Employment discrimination; Equity; Racism

Corporate Wasteland: The Landscape and Memory of Deindustrialization - Lewis, David; High, Steven C. (Between the Lines, 2007)
Deindustrialization is not simply an economic process; it is also a social and cultural phenomenon. The rusting detritus of our industrial past — the wrecked halls of factories, abandoned machinery too large to remove, and now useless infrastructures — has for decades been a part of the North American landscape. Through a unique blend of oral history, photographs, and interpretive essays, [this book] investigates this fascinating terrain and the phenomenon of its loss and rediscovery. --Publisher's description

Industrial Relations in Canada - McQuarrie, Fiona A. E. (Wiley and Sons Canada, 2007)
Makes it easier to understand the complex and sometimes controversial field of industrial relations. How? Its unique process-oriented approach gives you a clear road map by illustrating how and why unions are formed, and introduces you to the Canadian industrial relations system and the forces that shape it. --Publisher's description
Keywords: Industrial relations -- Canada -- Textbooks

Defining Work: Gender, Professional Work, and the Case of Rural Clergy - Mellow, Muriel (McGill-Queen's University Press, 2007)
An illuminating study of how gender and work intersect among the rural clergy. For rural clergy, the lines between private life and professional life can blur. Their offices are often in their homes, parishioners are also neighbours, and professional duties are intertwined with emotional caregiving and volunteer activity. In a society that defines work as paid, public, and intellectual the ambiguity inherent in the life of the rural clergy poses unique challenges. Muriel Mellow considers how men and women in this occupational group conceptualize "work" in the context of their unique circumstances and shows how their experience raises questions for feminist theories of work. Based on interviews with forty rural Protestant clergy, Mellow argues that male and female clergy challenge gendered definitions of work by focusing on obligation, context, visibility, and time. She also considers how clergy's work is shaped by the rural setting, arguing that we must consider how work is "placed" as well as gendered. --Publisher's description

Working People: An Illustrated History of the Canadian Labour Movement - Morton, Desmond (McGill-Queen's University Press, 2007)
From the dock workers of Saint John in 1812 to teenage "crews" at McDonald's today, Canada's trade union movement has a long, exciting history. Working People tells the story of the men and women in the labour movement in Canada and their struggle for security, dignity, and influence in our society. Desmond Morton highlights the great events of labour history - the 1902 meeting that enabled international unions to dominate Canadian unionism for seventy years, the Winnipeg General Strike of 1919, and an obscure 1944 order-in-council that became the labour's charter of rights and freedoms. He describes the romantic idealism of the Knights of Labor in the 1880s and looks at "new model" unions that used their members' dues and savings to fight powerful employers. Working People explores the clash between idealists, who fought for socialism, industrial democracy, and equality for women and men, and the realists who wrestled with the human realities of self-interest, prejudice, and fear. Morton tells us about Canadians who deserve to be better known - Phillips Thompson, Helena Gutteridge, Lynn Williams, Huguette Plamondon, Mabel Marlowe, Madeleine Parent, and a hundred others whose struggle to reconcile idealism and reality shaped Canada more than they could ever know. -- Publisher's description. Contents: Working people -- Getting organized -- International ideas -- Political movement -- Labour reformers -- Hinterland labour -- Trades and labour -- Gompers's shadow -- Business, labour, and governments -- Labour radicals -- Labour and the first World War -- Western revolt -- Unroaring twenties -- Surviving the depression -- Industrial unionism -- Fighting Hitler and management -- "People coming into their own" -- No falling back -- Struggle for allegiance -- Merger movement -- Times of frustration -- Prosperity and discontent -- Public Interest, Public Service -- Justice and nationalism -- Quebec and the common front -- Scapegoat for inflation -- Recession and hard times -- Levelling the playing field -- Struggling to the millennium -- Millennial achievements -- Graphs: Changes in the labour movement.
Keywords: Labor Unions; Labor movement; Working class

Confrontation, Struggle and Transformation: Organized Labour in the St. Catharines Area - Patrias, Carmela; Savage, Larry (Past CCLH Publications, 2007)
Confrontation, Struggle and Transformation is the story of working women and men in the St. Catharines area from the mid-1800s to the present. The study explores the labour movement's fight to survive and thrive in the Niagara region. Thanks to extensive quotations from interviews, archival sources and local newspapers, the story unfolds, in part, through the voices of the people themselves: workers who fought for unions, community members who supported them and employers who opposed them. --Publisher's description
Keywords: Discrimination in employment; History; Labor Unions; Labor movement; Political activity

Equity, Diversity, and Canadian Labour - Rayside, David M.; Hunt, Gerald (University of Toronto Press, 2007)
The Canadian labour movement has undergone several fundamental changes in response to demands for greater inclusion and representation by women, visible and sexual minorities, and people with disabilities. Equity, Diversity, and Canadian Labour explores the specific challenges put to outmoded conceptions of labour, charting the effort made towards establishing a more inclusive vision of labour in Canada. The study concludes that the Canadian labour movement has seen a fair amount of progress in this regard, though it still faces persistent impediments to equity and suffers from an uneven responsiveness within and across diversity issues. This collection of original essays brings together contributors from a variety of backgrounds womens studies, political science, sociology, industrial relations, and the labour movement itself. They provide detailed analyses of significant changes in union policies, practices, and cultures as viewed through different disciplinary lenses. With reference to gender, race, disability, and sexuality, the volume assesses the status of labour diversity in Canada and suggests what still needs to be done to advance the equity project. --Publisher's description. --Publisher's description. Contents: Looking back: A brief history of everything / Julie White -- Bargaining against the past: Fair pay, union practice, and the gender pay gap / Anne Forrest -- Union response to pay equity: A cautionary tale / Judy Haiven -- Labour's collective bargaining records on women's and family issues / Karen Bentham -- We are family: Labour responds to gay, lesbian, bisexual, and transgender workers / Gerald Hunt and Jonathan Eaton -- Broadening the labour movement's disability agenda / David Rayside and Fraser Valentine -- Racism and the labour movement / Tania Das Gupta -- Equity, diversity, and Canadian labour: A comparative perspective / David Rayside. Includes bibliographical references (pages 257-282).
Keywords: Activit politique. Mouvement ouvrier; Aspect social; Canada; Canada. Dmocratie syndicale; Canada. Genre/Form: Aufsatzsammlung; Canada. Labor movement; Canada. Labor movement. Labor union democracy. Labor unions; Canada. Labor union democracy; Canada. Labor unions; Canada. Pay equity; Canada. Syndicats; Canada. galit de rmunration; Labor unions; Political activity; Political activity. Labor unions; Social aspects; Social aspects. Pay equity. Arbeiterbewegung Gewerkschaft Syndicats

Labour and Employment Law in the Federal Public Service - Rootham, Christopher (Irwin Law, 2007)
[D]escribes the labour and employment law governing employees of Parliament, employees of government agencies, members of the RCMP, and most direct employees of the government (excluding members of the Canadian armed forces, judges, and employees of Crown corporations). Specifically, the book deals with the Public Service Labour Relations Act and the Public Service Employment Act. It also provides the leading cases and, where appropriate, a representative sample of decisions to explain or provide examples of particular points. The legal regime of the federal public service has undergone significant change in the past three years, and no other book addresses these significant changes. Part I of this book provides an overview of federal public service labour and employment law. Part II considers the normal labour law topics as they apply to direct employees of the government and employees of government agencies. Essentially, Part II of this book is about Part I of the Public Service Labour Relations Act. Part III concerns the terms and conditions of employment for both unionized and non-unionized employees — essentially, Part II of the Public Service Labour Relations Act. Part IV involves the legal regulation of the employment relationship in the federal public service — namely, the process for appointment to and within the federal public service. Part V of considers Crown servants — specifically RCMP members and parliamentary employees — who are not considered federal public servants for the purposes of the Public Service Labour Relations Act. Part VI considers the legal regulation of superannuation (pensions) for Crown servants and the role that courts play in the regulation of federal public service labour and employment law. --Publisher's description
Keywords: Canada; Civil service; Labor laws and legislation; Royal Canadian Mounted Police (RCMP)

Work in Tumultuous Times: Critical Perspectives - Shalla, Vivian; Clement, Wallace (McGill-Queen's University Press, 2007)
This interdisciplinary volume offers a powerful critique of how social structures and relations as well as ideologies shape workplaces, labour markets, and households in contemporary Canada. Contributors dissect recent transformations in work and expose the uncertainty, insecurity, and instability that increasingly characterize both paid and unpaid work. Using a progressive approach to political economy, contributors propose alternative policies and practices that might secure more decent livelihoods for workers and their families. -- Publisher's description
Keywords: Discrimination in employment; Job security; Labor

Labour Left Out: Canada's Failure to Protect and Promote Collective Bargaining as a Human Right - Adams, Roy J. (Canadian Centre for Policy Alternatives, 2006)
[The author] reports on his research into the failure of Canadian governments to protect and promote the collective bargaining rights of both unionized and non-unionized workers in this country. Far from honouring their solemn commitments to the UN’s International Labour Organization, our governments have blatantly and repeatedly violated them. Their many strike-breaking actions and arbitrarily imposed contract settlements have been condemned by the ILO, which has cited Canada as one of the world’s worst violators of basic labour rights. In exposing the appalling anti-labour record of our federal and provincial governments, Adams includes his exchange of correspondence with Canada’s labour ministries on their dismal labour-law policies. --Publisher's summary
Keywords: Collective bargaining -- Canada

Vers une transformation des relations industrielles en Amérique du Nord - Bernatchez, Jean-Claude (Gestion des relations humaines - Relations industrielles, 2006)
Dans un contexte où il semble impossible d’établir, ou encore de maintenir, un régime national de conditions de travail reflétant le niveau de prospérité observable dans les sociétés nord-américaines, la transformation des relations industrielles semble le moyen le plus sûr de rétablir l’équilibre entre le capital et le travail. En s’appuyant sur les fondements historiques des relations industrielles en Amérique du Nord, l’auteur dresse le portrait des syndicalismes américain, canadien et québécois, en tenant compte des lois qui les sous-tendent. Afin d’élaborer un nouveau régime de relations industrielles, il pose les principes à respecter et définit les étapes à franchir en vue d’instaurer de bonnes conditions de travail, garantissant ainsi une meilleure qualité de vie aux citoyens américains et canadiens. --Résumé de l'éditeur
Keywords: 2000-2099; 21e siècle; Amérique du Nord; Collective bargaining; Collective bargaining North America; Conditions de travail; Industrial relations; Industrial relations North America; North America; Négociation collective; Négociations collectives Amérique du Nord; Relations de travail; Relations industrielles; Relations industrielles Amérique du Nord; Syndicalisme; Travailleurs Amérique du Nord Conditions sociales 20e siècle; Travailleurs Amérique du Nord Conditions sociales 21e siècle; Working class North America Social conditions 21st century; Working class Social conditions; industrial relations

Social Reproduction: Feminist Political Economy Challenges Neo-Liberalism - Bezanson, Kate; Luxton, Meg (McGill-Queen's University Press, 2006)
How the unaccounted costs of neo-liberal policies fall on Canadian women. Using a feminist political economy approach, contributors document the impact of current socio-economic policies on states, markets, households, and communities. Relying on impressive empirical research, they argue that women bear the costs of and responsibility for care-giving and show that the theoretical framework provided by feminist analyses of social reproduction not only corrects the gender-blindness of most economic theories but suggests an alternative that places care-giving at its centre. In this illuminating study, they challenge feminist scholars to re-engage with materialism and political economy to engage with feminism. --Publisher's description. Contents: Introduction: Social Reproduction and Feminist Political Economy / Kate Bezanson and Meg Luxton (pages 3-10) -- Feminist Political Economy in Canada and the Politics of Social Reproduction / Meg Luxton (pages 11-44) -- Social Reproduction and Canadian Federalism / Barbara Cameron (pages 45-74) -- Whose Social Reproduction? Transnational Motherhood and Challenges to Feminist Political Economy / Sedef Arat-Koç (pages 75-92) -- Bargaining for Collective Responsibility for Social Reproduction / Alice De Wolff (pages 93-116) -- Privatization: A Strategy for Eliminating Pay Equity in Health Care / Marjorie Griffin Cohen and Marcy Cohen (pages 117-144) -- Crisis Tendencies in Social Reproduction: The Case of Ontario’s Early Years Plan / Leah F. Vosko (pages 145-172) -- The Neo-liberal State and Social Reproduction: Gender and Household Insecurity in the Late 1990s / Kate Bezanson (pages 173-214) -- Someone to Watch over You: Gender, Class, and Social Reproduction / Susan Braedley (pages 215-230) -- Motherhood as a Class Act: The Many Ways in Which “Intensive Mothering” Is Entangled with Social Class / Bonnie Fox (pages 231-262) -- Friends, Neighbours, and Community: A Case Study of the Role of Informal Caregiving in Social Reproduction / Meg Luxton (pages 263-92 ).

Push! The Struggle for Midwifery in Ontario - Bourgeault, Ivy Lynn (McGill-Queen's/Associated Medical Services (Hannah Institute) studies in the history of medicine, health, and society, 2006)
In the 1980s there were few midwives in Canada and their practice was neither legal nor officially recognized. Ontario midwives and their supporters pushed to integrate midwifery into provincial health care systems and by 1993 had established an internationally renowned model. Ivy Lynn Bourgeault analyses the struggle to professionalize midwifery in the context of the negotiations between women, as both consumers and providers of health care, and the state. Push! offers a historical account of the forces behind the integration of midwifery in Ontario, including public interest in funding midwifery services and the impact of political lobbying. Bourgeault also explores the specific features of Ontario's respected model, including the use of independent practitioners, funding for a self-regulatory college, a university-based education program, and the provision of midwifery care in both home and hospital settings. --Publisher's description
Keywords: Government policy; History; Home childbirth; Midwifery; Midwives; Ontario; Political aspects

The Hanging of Angélique: The Untold Story of Canadian Slavery and the Burning of Old Montréal - Cooper, Afua (Race in the Atlantic World, 1700-1900, 2006)
During the night of April 10, 1734, Montréal burned. Marie-Joseph Angélique, a twenty-nine-year-old slave, was arrested, tried, and found guilty of starting the blaze that consumed forty-six buildings. Suspecting that she had not acted alone and angered that she had maintained her innocence, Angélique's condemners tortured her after the trial. She confessed but named no accomplices. Before Angélique was hanged, she was paraded through the city. Afterward, her corpse was burned. Angélique, who had been born in Portugal, faded into the shadows of Canadian history, vaguely remembered as the alleged arsonist behind an early catastrophic fire. The result of fifteen years of research, [this book] vividly tells the story of this strong-willed woman. Afua Cooper draws on extensive trial records that offer, in Angélique's own words, a detailed portrait of her life and a sense of what slavery was like in Canada at the time. Predating other first-person accounts by more than forty years, these records constitute what is arguably the oldest slave narrative in the New World. Cooper sheds new light on the largely misunderstood or ignored history of slavery in Canada. She refutes the myth that Canada was a haven at the end of the Underground Railroad. Cooper also provides a context for Canada in the larger picture of transatlantic slavery while re-creating the tragic life of one woman who refused to accept bondage. --Publisher's description
Keywords: 18e siècle. Esclaves; 18e siècle. Fires. Slaves; 18e siècle. Noires; 18th century. Esclaves; Biographies. Esclavage; Biographies. Incendies; Biography. Fires; Canada; Commerce; Histoire; History; Montréal; Québec (Province); Slaves

Globalization and the Future of Labour Law - Craig, John D. R.; Lynk, Michael (Cambridge University Press, 2006)
How are national and international labour laws responding to the challenge of globalization as it re-shapes the workplaces of the world? This collection of essays by leading legal scholars and lawyers from Europe and the Americas was first published in 2006. It addresses the implications of globalization for the legal regulation of the workplace. It examines the role of international labour standards and the contribution of the International Labour Organization, and assesses the success of the European experiment with continental employment standards. It explores the prospects for hemispheric co-operation on labour standards in the Americas, and deals with the impact of international labour standards on the rights of women and migrant workers. As the nature and organization of work around the world is being decisively transformed, new regional and international institutions are emerging that may provide the platform for new labour standards, and for protecting existing ones. --Publisher's description
Keywords: Americas; Amériques; Droit du travail; European Union; Futur; Globalization; International Labour Organization; International labour law; Labor laws and legislation; Labor laws and legislation, International; Labour law; Labour standards; Mondialisation; Normes de travail; Normes internationales; Organisation internationale du travail; Travail (Droit international); UE/CE Union européenne

Women and Their Work in Upper Canada - Errington, Elizabeth Jane (Historical Booklet / Canadian Historical Association, 2006)

Red Light Neon: A History of Vancouver's Sex Trade - Francis, Daniel (Subway, 2006)
"This book is a history of hypocrisy." So begins Daniel Francis, BC's leading popular historian, as he explores the colourful and ultimately tragic story of prostitution in Vancouver. He writes: "The city's political and social leaders consistently have treated prostitutes as pariahs whose presence was tolerated, sometimes exploited, but never approved. All the while, the authorities collected millions of dollars in fines and licence fees from businesses that everyone knew were, and are, fronts for the sex trade." Working in long overlooked archives and drawing on personal interviews, Francis shows how in some ways commercial sex has been both a reflection and a result of Vancouver's essential character, with its tolerant social mores, ethnic diversity--and political opportunism. It's a tale that takes in mayors and masseuses, police chiefs and pimps, judges and johns. Francis explains: "Sex workers have never lacked for customers. What they have lacked is a secure place to conduct their business. A vast off-street sex trade flourished while police, at the urging of politicians vowing to purify the city, concentrated their attention on the comparatively small number of street prostitutes who worked out in the open. Because they were considered a nuisance, these sex workers were hounded from street to street and neighbourhood to neighbourhood [... These efforts salved the conscience of the morally righteous, but each attempt to discourage prostitution simply forced women to work in increasingly dangerous circumstances." The end result, ultimately, was the tragedy of the Missing Women--murdered sex workers from the Downtown Eastside--and the sensational criminal case that followed. --Publisher's description
Keywords: Prostitution -- British Columbia -- Vancouver -- History

Working on Screen: Representations of the Working Class in Canadian Cinema - Khouri, Malek; Varga, Darrell (University of Toronto Press, 2006)
As themes in film studies literature, work and the working class have long occupied a peripheral place in the evaluation of Canadian cinema, often set aside in the critical literature for the sake of a unifying narrative that assumes a division between Québécois and English Canada's film production, a social-realist documentary aesthetic, and what might be called a 'younger brother' relationship with the United States. In Working on Screen, contributors examine representations of socio-economic class across the spectrum of Canadian film, video, and television, covering a wide range of class-related topics and dealing with them as they intersect with history, political activism, globalization, feminism, queer rights, masculinity, regional marginalization, cinematic realism, and Canadian nationalism. Of concern in this collection are the daily lives and struggles of working people and the ways in which the representation of the experience of class in film fosters or marginalizes a progressive engagement with history, politics, and societies around the world. Working on Screen thus expands the scholarly debates on the concept of national cinema and builds on the rich, formative efforts of Canadian cultural criticism that held dear the need for cultural autonomy. -- Publisher's description

Paths to Union Renewal: Canadian Experiences - Kumar, Pradeep; Schenk, Christopher Robert (Broadview Press, 2006)
This book focuses on the efforts and progress of union revitalization and organizing, and documents the renewal initiatives undertaken by unions in Canada. Unions, separately or in coalition with other unions or social groups, have begun to re-examine the basis of their organization and activity in the face of a harsher economic and political climate. Signs of union renewal include increased rank-and-file participation in the life of the union, increased democratic decision-making, evidence of new horizontal union structures, the development of a worker-centred societal vision, and a new emphasis on organizing both internally and externally. Paths to Union Renewal addresses a subject of considerable political and social importance about which there have been a number of debates. A key impetus for this re-examination has originated in the United States where decades-long union decline has engendered new ideas adopted by a number of unions and the national central labour body the AFL-CIO. This in turn has led to debates on renewal strategies in Western Europe and Anglo-Saxon countries from Britain to Australia. Despite this, little detailed research of the processes, structures, and implications of union renewal has been undertaken across Canada. Paths to Union Renewal fills this gap by critically examining union renewal in a variety of unions, providing a basis for informed discussion and debate on the role and place of trade unions in contemporary society. --Publisher's description
Keywords: British Columbia Federation of Labour. Organizing Institute; British Columbia Government and Service Employees Union (BCGEU); Canadian Auto Workers (CAW); Canadian Union of Public Employees (CUPE); Communications, Energy and Paperworkers Union of Canada (CEP); Community unionism; Labor Unions; Labor movement; Organizational change; United Food and Commerical Workers (UFCW); United Steelworkers (USW)

Bloodletting & Miraculous Cures: Stories - Lam, Vincent. (Doubleday Canada, 2006)
Bloodletting & Miraculous Cures is a collection of mature and intricate stories connected through the relationships that develop among a group of young doctors as they move from the challenges of med school to the intense world of emergency rooms, evac missions, and terrifying new viruses. --Publisher's description. Contents: How to get into medical school, part I -- Take all of Murphy -- How to get into medical school, part II -- Code clock -- A long migration -- Winston -- Eli -- Afterwards -- An insistent tide -- Night flight -- Contact tracing -- Before light -- Glossary of terms -- Acknowledgements.
Keywords: Doctor; Medical Students; Physicians; Short Stories; White-collared work

Red Travellers: Jeanne Corbin and Her Comrades - Lévesque, Andrée (McGill-Queen's University Press, 2006)
Jeanne Corbin typifies the female militants of the first generation of Canadian Communists. Andrée Lévesque's powerful account of the experiences of Corbin and her female comrades reveals the essential role women played in the movement. Levesque also shows that, despite some efforts to construct egalitarian gender relations, these women subordinated gender issues to the class struggle. Corbin's red itinerary began when she joined the Young Communist League in Edmonton. She later held party posts across the country through her involvement with The Worker in Toronto, a French communist paper in Montreal, the Workers' Cooperative in Timmins, and a lumbermen's strike in Abitibi - where she was jailed for taking part in a protest. She died of tuberculosis in London, Ontario, in 1944. Levesque relies on a wide range of sources to provide a unique exploration of Canadian labour and social history. --Publisher's descriptioin

Social Reproduction: Feminist Political Economy Challenges Neo-Liberalism - Luxton, Meg; Bezanson, Kate (McGill-Queen's University Press, 2006)
Using a feminist political economy approach, contributors document the impact of current socio-economic policies on states, markets, households, and communities. Relying on impressive empirical research, they argue that women bear the costs of and responsibility for care-giving and show that the theoretical framework provided by feminist analyses of social reproduction not only corrects the gender-blindness of most economic theories but suggests an alternative that places care-giving at its centre. In this illuminating study, they challenge feminist scholars to re-engage with materialism and political economy to engage with feminism. -- Publisher's description
Keywords: Canada; Discrimination à l'égard des femmes Canada; Feminist economics; Feminist economics Canada; Feminist theory; Feminist theory Canada; Femmes Canada Conditions sociales; Femmes Canada Conditions économiques; SOCIAL SCIENCE Feminism & Feminist Theory; SOCIAL SCIENCE Sociology General; Sex discrimination against women; Sex discrimination against women Canada; Théorie féministe Canada; Women Canada Economic conditions; Women Canada Social conditions; Women Economic conditions; Women Social conditions; Économie féministe Canada

Canadian Working-Class History: Selected Readings - MacDowell, Laurel Sefton; Radforth, Ian Walter (Canadian Scholars' Press, 2006)
[This book updates] recent and classic scholarship on the history, politics, and social groups of the working class in Canada. Some of the changes...in the new edition include better representation of women scholars and nine provocative and ground-breaking new articles on racism and human rights; women's equality; gender history; Quebec sovereignty; and the environment. --Publisher's description
Keywords: Equality; History; Human rights; Labor Unions; Labor movement; Labour; Racism; Social history; Women; Working class; labour rights

Working Class Culture and the Development of Hull, Quebec, 1800-1929 - Martin, Michael (J. Bernier, 2006)
...This [book], most decidedly, is not only the narrative of the prominent citizens in the history of Hull. Rather, it is the story of thousands of virtually unknown men, women, and children of the working class of Hull, Quebec. Among many others, it’s the story of James McConnell, a worker from Nova Scotia, hired by Philemon Wright in Quebec City in 1801. It’s the story of Luther Colton, a carpenter from New York, who came to Hull in 1802. It’s the story of Joseph Delorme, one of the first French Canadians to be hired by Philemon Wright to work in his shanties, just to give three examples of normally unnamed workers. This study of the ordinary people of Hull reflects an agenda that emerged in the last half of the 20th century when historians came to see that “the real task of history in our time is to recreate, appreciate and analyze the full spectrum of past societies; that means, pre-eminently to attempt to understand the lives of the working people, the great mass of any society,” rather than merely the politicians and elites who governed past societies. This book also studies the workers who helped the workers of Hull forge an awareness of themselves as a class in a self-conscious attempt to improve the lot of ordinary working people. --Author's preface
Keywords: History; Hull (Gatineau, Québec) History; Hull (Gatineau, Québec) Social conditions; Québec Gatineau Hull; Social conditions; Working class; Working class Hull (Gatineau, Québec) History

Apprivoiser le syndicalisme en milieu universitaire: histoire du syndicat genéral des professeurs et professeures de l'Université de Montréal - Rouillard, Jacques (Boréal, 2006)
Un syndicat de professeurs d’université n’est pas un syndicat comme les autres. L’individualisme inhérent au travail et à la culture professorale a toujours contribué à rendre plusieurs d’entre eux méfiants et plutôt réservés face à la solidarité syndicale. Chez les professeurs, le « nous » syndical s’est graduellement construit, par étapes, parfois dans la tourmente et la division. C’est ce cheminement des universitaires, cet «apprivoisement» du syndicalisme, qui est l’objet de ce volume. La conscience syndicale chez les professeurs commence véritablement à prendre racine avec la création du Syndicat des professeurs en 1966. Elle aboutit à la formation du SGPUM en 1972 et à son accréditation trois ans plus tard. Dans les années 1980 et 1990 l’utilité du syndicalisme ne fait plus de doute chez les professeurs, frappés par de faibles augmentations salariales, quand ce n’est pas des gels et des récupérations. Dans les années 2000, leur solidarité se renforce avec l’objectif de rattrapage des conditions de travail qui va culminer avec la première grève des professeurs en hiver 2005. Jacques Rouillard propose ici un historique de quarante ans de vie syndicale et de plus de cinquante ans de vie associative. Soucieux également d’insérer l’évolution du syndicat dans la trame générale de l’histoire du syndicalisme québécois, il accorde une large place dans cet historique aux négociations des syndicats des secteurs public et parapublic. --Résumé de l'éditeur

Working in a Global Era: Canadian Perspectives - Shalla, Vivian (Canadian Scholars Press, 2006)
This progressive new reader examines work in a global era. It is an ideal text for sociology of work and labour courses across Canada. This book will also be relevant to a wide range of courses in labour studies and industrial relations programs in Canada." "Divided into eight key parts with a total of 16 essential readings, this volume covers a great deal of ground: Fordist and post-Fordist methods of work organization; labour markets in transition; working in the free-trade zones; migration, transnationalism, and domestic work; neo-liberalism and the dismantling of the welfare state; education, training, and skills in a knowledge-based economy; and the labour movement in transition. All major issues surrounding work in Canada are covered. Book jacket. --Publisher's description
Keywords: Labor -- Canada -- Textbooks

Home Economics: Nationalism and the Making of 'Migrant Workers' in Canada - Sharma, Nandita Rani (University of Toronto Press, 2006)
Home Economics is an urgent and much-needed reminder that society must pay careful attention to how nationalist ideologies construct ‘homelands’ that essentially leave the vast majority of the world's migrant peoples homeless. A massive shift has taken place in Canadian immigration policy since the 1970s: the majority of migrants no longer enter as permanent residents but as temporary migrant workers. In Home Economics, Nandita Sharma shows how Canadian policies on citizenship and immigration contribute to the entrenchment of a system of apartheid where those categorized as migrant workers live, work, pay taxes and sometimes die in Canada but are subordinated to a legal regime that renders them as perennial outsiders to nationalized Canadian society. In calling for a no borders policy in Canada, Sharma argues that it is the acceptance of nationalist formulations of home informed by racialized and gendered relations that contribute to the neo-liberal restructuring of the labour market in Canada. She exposes the ideological character of Canadian border control policies which, rather than preventing people from getting in, actually work to restrict their rights once within Canada. Home Economics is an urgent and much-needed reminder that in today's world of growing displacement and unprecedented levels of international migration, society must pay careful attention to how nationalist ideologies construct homelands that essentially leave the vast majority of the world's migrant peoples homeless. --Publisher's description
Keywords: Ausländischer Arbeitnehmer; Canada; Canada Emigration and immigration Government policy; Canada Émigration et immigration Politique gouvernementale; Capitalism; Capitalisme; Einwanderung; Electronic books; Emigration and immigration Government policy; Foreign workers Government policy; Foreign workers Government policy Canada; Globalization; Kanada; Kapitalismus; Mondialisation; Travailleurs étrangers Politique gouvernementale Canada; capitalism; globalism

The Struggle Against Wage Controls: The Saint John Story, 1975-1976 - Vair, George; Canadian Committee on Labour History (Past CCLH Publications, 2006)
In October 1976 one million Canadian workers walked off the job to protest the wage controls imposed by Prime Minister Pierre Elliott Trudeau. In a memorable personal account of this historic general strike, Saint John labour activist George Vair recalls how workers in one New Brunswick city mobilized to defend themselves and their unions and defeat the unpopular program. --Publisher's description
Keywords: General Strike, Saint John, N.B., 1976; Government policy; History; Labor movement; Strikes and lockouts; Wages

Precarious Employment: Understanding Labour Market Insecurity in Canada - Vosko, Leah F. (McGill-Queen's University Press, 2006)
This interdisciplinary volume offers a multifaceted picture of precarious employment and the ways in which its principal features are reinforced or challenged by laws, policies, and labour market institutions, including trade unions and community organizations. Contributors develop more fully the concept of precarious employment and critique outmoded notions of standard and nonstandard employment. The product of a five-year Community-University Research Alliance, the volume aims to foster new social, statistical, legal, political, and economic understandings of precarious employment and to advance strategies for improving the quality and conditions of work and health. --Publisher's description
Keywords: Industrial hygiene; Labor Unions; Labor laws and legislation; Labor market; Temporary employment

Mine Mill Fights Back: Mine Mill/CAW Local 598 Strike 2000-2001, Sudbury - Beck, Kaili; Kinsman, Gary; Steedman, Mercedes; Suschnigg, Peter; Bowes, Chris (Mine Mill / CAW Local 598, 2005)
Illustrated history of the 2000-2001 strike of the Mine Mill/Canadian Auto Workers Local 598 strike against Falconbridge in Sudbury, Ont. Published in collaboration with Laurentian University's Labour and Trade Union Studies' Program.
Keywords: History; Labor Unions; Mineral industries; Miners; Social aspects; Strikes and lockouts

Structure and Operation of the Steelworkers - Brasch, Hans (Journal Printers, 2005)
Abundantly illustrated update of "A Miner's Chronicle" from 1998 to 2004, that emphasizes union-related activities and events. Also includes a list of mining fatalities.
Keywords: History; Labor Unions; Miners; Sudbury, Ont.; United Steelworkers of America. Local 6500

From UI to EI: Waging War on the Welfare State - Campeau, Georges; Howard, Richard (Law and society series (Vancouver, B.C.), 2005)
Established in 1940 in response to the Great Depression, the original goal of Canada’s system of unemployment insurance was to ensure the protection of income to the unemployed. Joblessness was viewed as a social problem and the jobless as its unfortunate victims. If governments could not create the right conditions for full employment, they were obligated to compensate people who could not find work. While unemployment insurance expanded over several decades to the benefit of the rights of the unemployed, the mid-1970s saw the first stirrings of a counterattack as the federal government’s Keynesian strategy came under siege. Neo-liberalists denounced unemployment insurance and other aspects of the welfare state as inflationary and unproductive. Employment was increasingly thought to be a personal responsibility and the handling of the unemployed was to reflect a free-market approach. This regressive movement culminated in the 1990s counter-reforms, heralding a major policy shift. The number of unemployed with access to benefits was halved during that time. From UI to EI examines the history of Canada’s unemployment insurance system and the rights it grants to the unemployed. The development of the system, its legislation, and related jurisprudence are viewed through a historical perspective that accounts for the social, political, and economic context. Campeau critically examines the system with emphasis upon its more recent transformations. This book will interest professors and students of law, political science, and social work, and anyone concerned about the right of the unemployed to adequate protection. --Publisher's description. Contents: Why UI? -- The British Act of 1911 -- Developing a Canadian system -- The UI Act of 1940 -- UI expansion, 1940-75 -- Vision under siege, 1975-88 -- Rights enshrined in case law, 1940-90 -- The system hijacked, 1989-96 -- Onward to EI -- Case law in the neoliberal riptide of the 1990s. Translation of: De l'assurance-chômage à l'assurance-emploi.
Keywords: History; Law and legislation; Unemployment insurance

Self-Employed Workers Organize: Law, Policy, and Unions - Cranford, Cynthia; Fudge, Judy; Tucker, Eric; Vosko, Leah F. (McGill-Queen's University Press, 2005)
Over a million self-employed Canadians work every day but many of them are not entitled to the basic labour protections and rights such as minimum wages, maternity and parental leaves and benefits, pay equity, a safe and healthy working environment, and access to collective bargaining. The authors of "Self-Employed Workers Organize" offer a multi-disciplinary examination of the legal, political, and social realities that both limit collective action by self-employed workers and create huge impediments for unions attempting to organize them. Through case studies of newspaper carriers, rural route mail couriers, personal care workers, and freelance editors - four groups who have led pioneering efforts to organize - the authors provide a window into the ways political and economic conditions interact with class, ethnicity, and gender to shape the meaning and strategies of working men and women and show how these strategies have changed over time. They argue that the experiences of these workers demonstrate a pressing need to expand collective bargaining rights to include them. --Publisher's description
Keywords: Case studies; Labor unions; Legal status, laws, etc.; Organizing; Self-employed

Discounted Labour: Women Workers in Canada, 1870-1939 - Frager, Ruth A.; Patrias, Carmela (Themes in Canadian history, 2005)
The years between 1870 and 1939 were a crucial period in the growth of industrial capitalism in Canada, as well as a time when many women joined the paid workforce. Yet despite the increase in employment, women faced a difficult struggle in gaining fair remuneration for their work and in gaining access to better jobs. Discounted Labour analyses the historical roots of women's persistent inequality in the paid labour force. Ruth A. Frager and Carmela K. Patrias analyse how and why women became confined to low-wage jobs, why their work was deemed less valuable than men's work, why many women lacked training, job experience, and union membership, and under what circumstances women resisted their subordination. Distinctive earning discrepancies and employment patterns have always characterized women's place in the workforce whether they have been in low-status, unskilled jobs, or in higher positions. For this reason, Frager and Patrias focus not only on women wage-earners but on women as salaried workers as well. They also analyze the divisions among women, examining how class and ethnic or racial differences have intersected with those of gender. Discounted Labour is an essential new work for anyone interested in the historical struggle for gender equality in Canada. --Publisher's description
Keywords: 19th century; 20th century; Canada; Employment; History; Sexual division of labor; Women

Bora Laskin: Bringing Law to Life - Girard, Philip (Published for the Osgoode Society for Canadian Legal History by University of Toronto Press, 2005)
In the history of twentieth-century Canadian law, Bora Laskin (1912-1984) is by all accounts one of its most important figures. Born in northern Ontario to Russian-Jewish immigrant parents, Laskin became a prominent human rights activist, university professor, and labour arbitrator before embarking on his 'accidental career' as a judge on the Ontario Court of Appeal, a member of the Supreme Court of Canada, and Chief Justice of Canada. Throughout his entire professional life, he used the law to make Canada a better place for workers, racial and ethnic minorities, and the disadvantaged. As a judge, he sought to make the judiciary more responsive to changing expectations in regard to justice and fundamental rights." "In this biography, Philip Girard chronicles the life of a man who fought corporate capital, university boards, the Law Society of Upper Canada, and his own judicial colleagues in an effort to modernize institutions and reshape Canadian law. Girard draws on a wealth of previously untapped archival sources to provide, in vivid detail, a critical assessment of the contributions of a dynamic man on an important mission. --Book cover description
Keywords: Biographies; Biographies, memoirs and correspondance; Canada; Canada. Cour suprême Biographies; Canada. Supreme Court; Canada. Supreme Court Biography; Canada. Supreme Court History; Electronic books; Judges; Judges Canada Biography; Juges Canada Biographies; Laskin, Bora; Supreme court

Ontario Public Service Employment & Labour Law - Hadwen, Timothy; Eady, Don; Marvy, Leonard; Strang, David (Irwin Law, 2005)
This book deals with the Crown Employees Collective Bargaining Act and the Public Service Act, the statutes that primarily govern unionized and non-unionized employment and labour relations in the Ontario Public Service and Crown Agencies. The book provides a full review of all sections, and all judicial and arbitral consideration, of both acts. It also discusses the unique treatment of the Crown and its employees in the Public Sector Labour Relations Transition Act and the Employment Standards Act.
Keywords: Civil service; Collective labor agreements; Employee-management relations in government; Government employees; Law and legislation; Ontario

The Workers' Festival: A History of Labour Day in Canada - Heron, Craig; Penfold, Steve (University of Toronto Press, 2005)
For most Canadians today, Labour Day is the last gasp of summer fun: the final long weekend before returning to the everyday routine of work or school. But over its century-long history, there was much more to the September holiday than just having a day off. In The Workers' Festival, Craig Heron and Steve Penfold examine the complicated history of Labour Day from its origins as a spectacle of skilled workers in the 1880s through its declaration as a national statutory holiday in 1894 to its reinvention through the twentieth century. The holiday's inventors hoped to blend labour solidarity, community celebration, and increased leisure time by organizing parades, picnics, speeches, and other forms of respectable leisure. As the holiday has evolved, so too have the rituals, with trade unionists embracing new forms of parading, negotiating, and bargaining, and other social groups re-shaping it and making it their own. Heron and Penfold also examine how Labour Day's monopoly as the workers' holiday has been challenged since its founding, with alternative festivals arising such as May Day and International Women's Day. The Workers' Festival ranges widely into many key themes of labour history - union politics and rivalries, radical movements, religion (Catholic and Protestant), race and gender, and consumerism/leisure - as well as cultural history - public celebration/urban procession, urban space and communication, and popular culture. From St. John's to Victoria, the authors follow the century-long development of the holiday in all its varied forms. --Publisher's description

Madeleine Parent: Activist - Lévesque, Andrée; Lévesque, Andrée (Sumach Press, 2005)
"[B]rings together some of the papers presented at the conference, "Madeleine Parent, ses lutes et ses engagements /Madeleine Parent and her struggles," held in March 2001 at McGill University under the auspices of the Quebec Studies Programme and the McGill Centre for Research and Teaching on Women." -- Editor. Translation of: Madeleine Parent, militante (2003). Contents: Portfolio of photographs -- Introduction: setting the stage; Student life at McGill, 1936-1940 / Andrée Lévesque -- Textile strikes in Quebec: 1946, 1947, 1952 / Denyse Baillargeon -- Carrying on the struggle in Ontario, 1952-1973 / John Lang -- The Atlantic connection / John St-Amand -- The women's movement in Canada: setting the agenda / Lynn Kaye & Lynn Mcdonald  -- The importance of being Madeline: how an inactivist won the heart of Quebec's immigrant and minority women -- A tribute to a valiant lady / Françoise David -- Madeleine Parent: an unfailing ally of native women / Michèle Rouleau -- An iron will and a string of pearls / Rick Salutin -- A friend, a role model / Monique Simard.
Keywords: Feminism; History; Parent, Madeleine, 1918-2012; Social conditions; Syndicalism; Women political activists

Global Game, Local Arena: Restructuring in Corner Brook, Newfoundland - Norcliffe, Glen (Social and economic studies (St. John's, NL), 2005)
In Global Game, Local Arena, geographer Glen Norcliffe explores how powerful forces of global economic integration have played out in Corner Brook and interprets the town's creation as a company town in the colonial era, its slow transformation into a public municipality, and the phase of vigorous restructuring launched in 1984 to raise the paper mill's performance in response to increased global competition. Restructuring introduced lean production, and in turn this impacted on workers' families, and on the larger community. Through extensive interviews with former and present mill workers and their families, and by examining written records — newspaper accounts, legislative acts, earlier published sources — the author sheds valuable light on how the process of globalization has played out in one small but typical local arena. Since 1984 Corner Brook has experienced large-scale out-migration of younger adults, and a rapid aging of the population. Community resistance to this process has been mostly subtle, taking the form of a reconnection to the population's local roots in outports and the woods. --Publisher's description

Ma vie de syndicaliste - Parrot, Jean-Claude (Boréal, 2005)
Pendant quinze ans, Jean-Claude Parrot a occupé le poste de président du Syndicat des travailleurs et travailleuses des postes, et pendant plus de dix-huit ans, il en a été le négociateur en chef. Au cours de toutes ces années, le leadership de Jean-Claude Parrot a fait de ce syndicat un des plus militants et des plus démocratiques au Canada. Quand Pierre Elliott Trudeau a décidé de transformer le service postal en société de la Couronne, c’est Parrot qui était à la barre. C’est lui également qui a supervisé la fusion des divers syndicats des postiers en un seul grand syndicat. Jean-Claude Parrot raconte ici son histoire, mais en même temps celle de la formation d’une grande union syndicale. Il raconte également comment la démocratie syndicale s’est construite – comment les membres de la base ont pu s’imposer dans tout le mécanisme de prise de décisions. Ce livre nous permet de suivre la carrière de l’un des plus grands dirigeants syndicaux du Canada, de le voir engagé dans son combat pour donner une voix aux travailleurs. Dans ce combat, Parrot a souvent placé son engagement syndical avant sa vie privée, et il a préféré faire de la prison plutôt que de sacrifier ses principes. À travers le récit de Jean-Claude Parrot, nous voyons la démocratie en marche, nous voyons le combat d’un homme pour défendre la cause des travailleurs et des syndicats. Traduit de l'anglais (Canada) par Claire Laberge --Résumé de l'éditeur

My Union, My Life: Jean-Claude Parrot and the Canadian Union of Postal Workers - Parrot, Jean-Claude (Fernwood, 2005)
Jean-Claude Parrot was National President of the Canadian Union of Postal Workers for fifteen years and its chief negotiator for eighteen. During that time he provided the leadership which built what became Canada’s most militant and democratic union. When Pierre Trudeau decided to make the post office a crown corporation Parrot was there to guide the transition. He was also there to oversee the merger of the various postal unions into “one union for all.” As well as Jean-Claude Parrot’s story, this is also the story of the formation of a union. It is a story of how union democracy was built–of how the grassroots union membership became an integral part of decision making in the union. In the pages of this book you will follow the life of one of Canada’s greatest union leaders as he fought to give the workers a voice. In the course of the struggle Parrot often put his union work and commitments before his own personal life and spent time in prison rather than sacrifice his principles and the cause of the workers in the union. Through Parrot’s recounting of these years we learn about how the struggle was waged, how democracy was built and how a union leadership worked tirelessly in the service of the union membership. --Publisher's description
Keywords: Biography; Canadian Union of Postal Workers; Officials and employees; Parrot, Jean-Claude; Postal service

What Do They Call a Fisherman?: Men, Gender, and Restructuring in the Newfoundland Fishery - Power, Nicole Gerarda (Social and economic studies (St. John's, NL), 2005)
Newfoundland fisheries have been transformed from an industry once dominated by petty commodity production and merchant-fisher relations to one dominated by private enterprise and corporate capitalism. State efforts to enclose the fisheries through boat quotas and to limit participation through a core classification system demonstrate a shift in values. Science-based regulation, in which the estimates of fisheries scientists were overly optimistic, led to the collapse of the cod fishery. The recent turn to a fishery based on classical economics, emphasizing professionalization, has left inshore fishers caught between two value systems. The traditional view valorizes hard work and local knowledge about the fishing environment; the modern view embraces technology, rationalization and professionalization. In [this book] Nicole Power examines, through a feminist lens, how this tension between two views — between a way of life and a way to make a living — and how these changes have affected men (and women) in the Bonavista and Trinity Bays inshore fishery. Has a "crisis of fish" and the loss or diminution of livelihood led to a "crisis of masculinity"? Through extensive interviews with fishers and fish-plant workers, the author discovers that men have responded to restructuring in complex ways that are mediated, enabled and constrained by their class and gender positions, and by maritime cultural values and practices. --Publisher's description

The Tyranny of Work: Alienation and the Labour Process - Rinehart, James W. (Nelson, 2005)
[E]xamines the institution of work from the perspective of alienated labour, a perspective that many conventional approaches to the subject have ignored or misrepresented. Completely updated to reflect current trends in the labour force and research in the field of labour studies, The Tyranny of Work begins with a thorough discussion of work as a social problem and the sources of alienation. The book then examines the development of industrial capitalism in Canada, the white-collar and blue-collar worlds, and, finally, solutions to the problem of alienated labour. All statistics and data have been updated to reflect the most current research. Information from the 2001 Census has been integrated throughout the text. The Tyranny of Work examines the institution of work from the perspective of alienated labour, a perspective that many conventional approaches to the subject have ignored or misrepresented. --Publisher's description
Keywords: Alienation (Social psychology); Labor; Working class

Labour in the Laboratory: Medical Laboratory Workers in the Maritimes, 1900-1950 - Twohig, Peter (McGill-Queen's/Associated Medical Services (Hannah Institute) studies in the history of medicine, health, and society, 2005)
Medical laboratory technology is currently the third largest health profession in Canada but those who work in it remain largely invisible, both to the public and in the literature. In Labour in the Laboratory Peter Twohig examines the origins of the laboratory workforce in the Maritime provinces and rethinks the broader history of the twentieth-century Canadian hospital. --Publisher's description.
Keywords: 20th century; Biomedical technology; History; Hospital laboratories; Maritime Provinces; Medical Laboratory Personnel; Medical technologists

On the Side of the People: A History of Labour in Saskatchewan - Warren, Jim W.; Carlisle, Kathleen (Coteau Books, 2005)
A comprehensive history of working people in Saskatchewan, from the mid-1800s to the present, in a handsome coffee-table format, including numerous historical photos of the personalities and events that bring it to life. This book is created for the working people that it celebrates. In a plain-spoken and engaging narrative style, it captures the events and the personalities that shaped the working people of Saskatchewan, and the life of the province that those workers built. Jim Warren tells the fascinating tale of jobs, working conditions, and the attempts to effect meaningful changes in the condition of workers' lives. Starting with the Fur Trade period, and moving through the arrival of the railroad brotherhoods, the emergence of the craft unions, two world wars, modernization, and into the present age, Working in Saskatchewan shows the evolution of the work force, and the relationship between that work force and both private and public sector employers. The book wraps up with a short chapter on the imagined future of labour in the province, in the voices of a series of speakers ranging from former Premier Allan Blakeney to ordinary workers on the floor of a recent SFL convention. Working in Saskatchewan also includes a number of features that will make it even more useful for private study or school work. Two comprehensive indexes detail the chief characters who played a role in the development of the labour movement, and a list of events and important topics. A series of informational appendices present statistical information relating to the Saskatchewan labour force - size of the organized and unorganized labour force, number of women in the work force, etc. There will also be a helpful glossary of the acronyms and abbreviations that characterize written or oral discussions about labour, and a "genealogy of labour" which charts the rise and growth of certain unions and their transformation into, or absorption by, others. --Publisher's description
Keywords: History; Labor movement; Labor movement Saskatchewan History; Labor unions; Labor unions Saskatchewan History; Mouvement ouvrier Saskatchewan Histoire; Saskatchewan; Saskatchewan Conditions sociales; Saskatchewan Social conditions; Social conditions; Syndicats Saskatchewan Histoire; Travailleurs Saskatchewan Histoire; Working class; Working class Saskatchewan History

Canadian Bolsheviks: The Early Years of the Commmunist Party of Canada - Angus, Ian (Trafford, 2004)
Canadian communism did not spring out of the ground suddenly at the end of World War I, and it was not smuggled into the country by Russian agents. The men and women who built the new movement were long-time socialist and labour militants in Canada. Inspired by the Russian Revolution and by their own experiences as leaders of the post-war labour revolt in Canada, they set about to create a new kind of party, one that could lead the fight for workers' power. The new Communist Party, formed between 1919 and 1921, quickly became the largest party on the left, with strong roots and influence in the unions and basic industry. Its members led heroic strikes. They fought for labor unity, and engaged in united electoral activity with other currents in the workers movement. They were in the forefront of the struggle for democratic rights. Ten years later, the party was destroyed. Most of its founding leaders were expelled, and three quarters of its membership dropped out. The Communist Party abandoned the program it had adopted in its early years, and turned its back on its principles. The organization still called itself Communist, but it was now "Tim Buck's Party." It had been transformed from a revolutionary party into an agent of the new ruling caste in Moscow. In Canadian Bolsheviks, Ian Angus describes and explains the first attempt to build a Leninist party on Canadian soil, showing why it succeeded so well at first, and why it ultimately failed. The second edition of a book that has been widely hailed as a pathbreaking work, "the best yet to appear" on the origins of Canadian communism. --Publisher's description

Survival: A Thematic Guide to Canadian Literature - Atwood, Margaret. (McClelland & Stewart, 2004)
When first published in 1972, Survival was considered the most startling book ever written about Canadian literature. Since then, it has continued to be read and taught, and it continues to shape the way Canadians look at themselves. Distinguished, provocative, and written in effervescent, compulsively readable prose, Survival is simultaneously a book of criticism, a manifesto, and a collection of personal and subversive remarks. Margaret Atwood begins by asking: "What have been the central preoccupations of our poetry and fiction?" Her answer is "survival and victims." Atwood applies this thesis in twelve brilliant, witty, and impassioned chapters; from Moodie to MacLennan to Blais, from Pratt to Purdy to Gibson, she lights up familiar books in wholly new perspectives. This new edition features a foreword by the author. --Publisher's description.
Keywords: Canadian Literature; Criticism

Common and Contested Ground: A Human and Environmental History of the Northwestern Plains - Binnema, Ted (University of Toronto Press, 2004)
In Common and Contested Ground, Theodore Binnema provides a sweeping and innovative interpretation of the history of the northwestern plains and its peoples from prehistoric times to the Lewis and Clark Expedition. The real history of the northwestern plains between a.d. 200 and 1806 was far more complex, nuanced, and paradoxical than often imagined. Drawn by vast herds of buffalo and abundant resources, bands of Indians, fur traders, and settlers moved across the northwestern plains establishing intricate patterns of trade, diplomacy, and warfare. In the process, the northwestern plains became a common and contested ground. Drawing on a wide range of sources, Binnema examines the impact of technology on the peoples of the northern plains, beginning with the bow-and-arrow and continuing through the arrival of the horse, European weapons, Old World diseases, and Euroamerican traders. --Publisher's description
Keywords: Ethnic relations; Fourrures Commerce Grandes Plaines Histoire; Fur trade; Fur trade Great Plains History; Grandes Plaines Relations interethniques; Great Plains; Great Plains Ethnic relations; History; Indianen; Indians of North America; Indians of North America Commerce; Indians of North America Commerce Great Plains History; Indians of North America Great Plains History; Indiens d'Amérique Commerce Grandes Plaines Histoire; Indiens d'Amérique Grandes Plaines Histoire

Workplace Learning: A Critical Introduction - Bratton, John; Sawchuk, Peter H.; Helms Mills, Jean C.; Pyrch, Timothy (Garamond Press, 2004)
This innovative book is concerned with the power relations, complexities, and contradictions in the paid workplace. Workplace learning is not value-free or politically neutral, and cannot be studied independently of the political economy of work. [This book] is part of a growing body of work that offers an alternative to mainstream approaches to workplace learning, recognizing that power relations, politics and conflicts of interest all shape learning. The authors emphasize the lived experiences of working people, avoiding prescriptive accounts and uncritical Human Resource Development views. --Publisher's description. Contents: 1. Introduction -- 2. Management strategies and workplace learning -- 3. Groups, teams and workplace learning -- 4. Organizational learning and learning organizations -- 5. Unions and workplace learning -- 6. Adult education, learning and work -- 7. Toward the future of workplace learning. Includes bibliographical references (p. [181]-194) and index.
Keywords: Adult education; Employees; Experiential learning; Training of

Le quatuor d'asbestos : autour de la grève de l'amiante - Delisle, Esther; Malouf, Pierre K. (Collection Histoire et société (Montréal), 2004)
Comme son titre l'indique, Le Quatuor d'Asbestos est composé de quatre livres, qui replacent dans son contexte historique la fameuse grève de l'amiante de 1949. De nombreux documents y sont présentés pour la première fois ; tous les points de vue y sont exprimés, car ici l'histoire est racontée par ceux qui l'ont vécue. On constatera, entre autres choses, que l'ouvrage publié en 1956 sous la direction de Pierre Trudeau, La Grève de l'amiante, donne une interprétation très réductrice, voire mensongère des causes et des conséquences de la grève. Tout commence donc en mars 1948 avec la publication dans la revue Relations d'un article retentissant du journaliste franco-américain Burton LeDoux sur les conditions de vie inhumaines des mineurs de Saint-Rémi d'Amherst dans les Laurentides. Cet article se veut la première étape dans une campagne pour l'amélioration de l'hygiène industrielle au Québec. Mais le gouvernement de Maurice Duplessis vient de céder le monopole du développement de l'Ungava aux intérêts financiers qui traitent comme du bétail les mineurs de Saint-Rémi. Avec la complicité de Mgr Joseph Charbonneau, les compagnies et le gouvernement musèlent Relations. Le Devoir prend alors le relais et publie en janvier 1949 un deuxième article de Burton LeDoux, qui révèle l'existence à East Broughton dans la région de l'amiante d'un autre abattoir humain. Un mois plus tard, la grève éclate à Asbestos et à Thetford Mines. La première revendication des mineurs : l'élimination de la poussière. Les travailleurs sont galvanisés, car c'est de leur santé et de leur vie mêmes qu'il s'agit. La grève durera quatre mois et demi, mais sera, surtout sur la question essentielle de l'hygiène industrielle, un échec total. Il faudra attendre 1975 pour qu'on décide enfin de corriger une situation qui aurait pu et dû l'être un quart de siècle plus tôt. Ensuite, il y aura la nationalisation et le déclin de l'industrie. Mais c'est une histoire qui n'a pas de fin et il se publie encore de nos jours des articles qui confirment que Burton LeDoux avait vu clair dès 1948. --Résumé de l'éditeur
Keywords: 1900-1999; Asbestos Strike, Québec, 1949; Grève de l'amiante, Québec, 1949; Grèves et lock-out Mines d'amiante Québec (Province) Histoire; Grèves et lock-out Mines d'amiante Québec (Province) Histoire Sources; Grèves et lock-out Mines d'amiante Québec (Province) Val-des-Sources; History; Québec; Québec Asbestos; Silicose; Silicose Québec (Province) Histoire 20e siècle; Silicosis; Silicosis Québec (Province) History 20th century; Sources; Strikes and lockouts Asbestos mining; Strikes and lockouts Asbestos mining Québec (Province) Asbestos; Strikes and lockouts Asbestos mining Québec (Province) History; Strikes and lockouts Asbestos mining Québec (Province) History Sources

The Paradox of American Unionism: Why Americans Like Unions More Than Canadians Do, But Join Much Less - Lipset, Seymour Martin; Meltz, Noah M.; Katchanovski, Ivan; Gomez, Rafael (ILR Press, 2004)
Why have Americans, who by a clear majority approve of unions, been joining them in smaller numbers than ever before? This book answers that question by comparing the American experience with that of Canada, where approval for unions is significantly lower than in the United States, but where since the mid-1960s workers have joined organized labor to a much greater extent. Given that the two countries are outwardly so similar, what explains this paradox? This book provides a detailed comparative analysis of both countries using, among other things, a detailed survey conducted in the United States and Canada by the Ipsos-Reid polling group. The authors explain that the relative reluctance of employees in the United States to join unions, compared with those in Canada, is rooted less in their attitudes toward unions than in the former country's deep-seated tradition of individualism and laissez-faire economic values. Canada has a more statist, social democratic tradition, which is in turn attributable to its Tory and European conservative lineage. Canadian values are therefore more supportive of unionism, making unions more powerful and thus, paradoxically, lowering public approval of unions. Public approval is higher in the United States, where unions exert less of an influence over politics and the economy. --Publisher's description
Keywords: Labor movement; Labor unions; Mouvement ouvrier; Syndicats; trade unions

Hidden Knowledge: Organized Labour in the Information Age - Livingstone, D. W.; Sawchuk, Peter H. (Peter Harold); Roth, Reuben N.; Martin, D'Arcy; Morgan, Clara (Garamond Press, 2004)
This book offers an original contribution to understanding an often-ignored aspect of our knowledge society and the much-heralded ‘knowledge-based economy.’ It decisively explodes the dual myths that working-class adults have inferior learning capacities and that talented youths naturally leave blue-collar careers. Livingstone and Sawchuk document the genuine learning practices of working-class people in unprecedented detail, using richly textured accounts of prior school experiences; current adult education course participation; and a wide array of learning resources in paid workplaces, households, and community settings. The authors criticize dominant theories of learning and work and develop an alternative explanation of working-class adult learning. Their analysis, grounded in the specific practices of everyday life, pays careful attention to the ways in which differential economic power, labor processes, sectoral contexts, union cultures, and access to organized educational resources shape individual and collective learning activities. The book also provides a reflective discussion of research processes suitable for democratic knowledge production in partnership with workers and their organizations, as well as workers' own practical recommendations for changes in learning and work relations. --Publisher's description. Contents: Introduction: Dimensions of learning and work in the knowledge society -- Pt. 1. Researching learning and work. Starting with Workers and Researching the "Hard Way" / with D'Arcy Martin -- Beyond cultural capital theories: Hidden dimensions of working-class learning. Pt. 2. Case studies.  Auto workers: Lean manufacturing and rich learning / with Reuben Roth -- Building a workers' learning Culture in the Chemical Industry -- Learning, Restructuring and job segregation at a community college -- Divisions of labour / Divisions of learning in a small parts manufacturer -- Garment workers: learning under disruption / with Clara Morgan. Pt. 3. Comparative perspectives across case studies. Household and community-based learning: Learning cultures and class differences beyond paid work -- Surfacing the hidden dimension of the knowledge society: the struggle for knowledge across differences. Includes bibliographical references (p. [299]-309) and index.
Keywords: Adult learning; Canada; Case studies; Education; Information society; Interviews; Labor union members; Labor unions; Occupational training; Working class - Effect of technological innovations on

Racism, Eh?: A Critical Inter-Disciplinary Anthology of Race and Racism in Canada - Nelson, Charmaine; Nelson, Camille A. (Captus Press, 2004)
"Racism, Eh?" is the first publication that examines racism within the broad Canadian context. This anthology brings together some of the visionaries who are seeking to illuminate the topics of race and racism in Canada through the analysis of historical and contemporary issues, which address race and racism as both material and psychic phenomena. Fundamentally interdisciplinary in nature, this text will be an invaluable resource for undergraduate and graduate students, academics studying or practicing within the Humanities and the Social Sciences, and anyone seeking information on what has been a little explored and poorly understood Canadian issue."--Publisher's description. Contents: Part 1 Institutional Racism -- 1 Penn and Teller Magic -- 2 Lance Belanger's Tango Lessons -- 3 The Black Occupational Structure in Late-Nineteenth-Century Ontario -- Part 2 Crime and Justice -- 4 Raising Raced and Erased Executions in African-Canadian Literature -- 5 Examining Racism and Criminal Justice -- 6 Criminological Research on "Race" in Canada -- Part 3 First Nations -- Of Land, Law and Power -- 7 Across a Boundary of Lava -- 8 Treaty Federalism -- 9 Navigating Discrimination -- Part 4 Race, Place and Nation -- 10 Adrift in the Diaspora -- 11 Racism Between Jews -- 12 Local Colour -- Part 5 Complexity of Intersectionallity and Performance of Racial Identity -- 13 Speak White! -- 14 Jack Canuck Meets John Chinaman -- 15 Performing Desire -- Part 6 Popular Culture -- 16 Race In-Out of the Classroom -- 17 Other Canadian Voices -- 18 (Re)Visioning Histories -- Part 7 Production and Representation -- 19 Each Sentence Realized or Dreamed Jumps Like a Pulse with History and Takes a Side -- 20 Articulating Spaces of Representation -- 21 The "Hottentot Venus" in Canada -- 22 Racial Recognition Underpinning Critical Art -- Part 8 Multiculturalism -- 23 But Where Are You REALLY From? -- 24 Social Cohesion and the Limits of Multiculturalism in Canada -- 25 Racialising Culture-Culturalising Race -- 26 Re-articulating Multiculturalism.
Keywords: Racism -- Canada

CCF Colonialism in Northern Saskatchewan: Battling Parish Priests, Bootleggers, and Fur Sharks - Quiring, David M. (UBC Press, 2004)
Saskatchewan's Co-operative Commonwealth Federation (CCF) the forerunner of the NDP, is often remembered for its humanitarian platform and its pioneering social programs. But during the twenty years it governed, it wrought a much less scrutinized legacy in the northern regions of the province." "Until the 1940s, churches, fur traders, and other influential newcomers held firm control over Saskatchewan's northern region. Following its rise to power in 1944 the CCF made aggressive efforts to unseat these traditional powers and install a new socialist economy and society in largely Aboriginal communities. The next two decades brought major changes to the region as well-meaning government planners grossly misjudged the challenges that confronted the north and failed to implement programs that would meet its needs. Northerners lacked the voice and political clout to determine policies for their half of the province and the CCF effectively created a colonial apparatus, imposing its own ideas and plans in those communities without consulting residents. While it did ensure that parish priests, bootleggers, and fur sharks no longer dominated the north, it failed to establish a workable alternative." "In written history that documents the colonial relationship between the CCT and northern Saskatchewan, David Quiring draws on extensive archival research and oral history to offer a fresh look at the CCF era. This examination will find an audience among historians of the north. Aboriginal scholars and general readers interested in Canadian history."--Publisher's description. Contents: Pt. 1. At the crossroads -- 1. Another country altogether -- Pt. 2. Building the colonial structure -- 2. From the top -- 3. Ultimate solution -- 4. Deterrent to development -- Pt. 3. Segregated economy -- 5. Never before have we been so poor -- 6. At the point of a gun -- 7. Just one jump out of the stone age -- 8. Pre-industrial way of life -- Pt. 4. Poverty-stricken and disease-ridden -- 9. Scarcely more than palliative -- 10. Dollars are worth more than lives -- Epilogue : we will measure our success -- A. Comments on collection of oral history -- B. Electoral record.
Keywords: Saskatchewan; Socialism

Le syndicalisme québécois : deux siècles d'histoire - Rouillard, Jacques (Boréal, 2004)
Contrairement à ce qu’on a cru pendant longtemps, l’histoire du syndicalisme au Québec remonte au début du XIXe siècle et évolue sensiblement au même rythme que celle des autres mouvements syndicaux en Amérique du Nord. À ce chapitre, les facteurs économiques et géographiques qui la rattachent au continent pèsent aussi lourd que le caractère distinct de la société québécoise. Voilà un des éléments clés qui ressortent du vaste pano-rama du syndicalisme au Québec que Jacques Rouillard trace ici. À chacune des périodes étudiées, qui renvoient aux grands moments de l’histoire occidentale, l’auteur montre comment les syndicats ont représenté une composante essentielle de la classe ouvrière et l’un des principaux lieux de contestation de l’ordre établi. Ce livre est une nouvelle édition de la première synthèse sur le syndicalisme québécois que Jacques Rouillard faisait paraître au Boréal en 1989. Ce nouveau texte, entièrement refondu, a été augmenté non seulement pour relater les événements qui se sont déroulés de 1985 à 2003, mais également pour tenir compte, aux diverses époques, des fruits de la négociation collective et de l’avancement de la recherche historique dans ce domaine. --Résumé de l'éditeur

Challenging the Market: The Struggle to Regulate Work and Income - Stanford, Jim; Vosko, Leah F. (McGill-Queen's University Press, 2004)
Challenging the Market offers insights from eighteen scholars and activists from around the world. Calling on a tremendous range of experience in different countries, different industries, and with different groups of workers, contributors argue that labour market policy should shift to a more interventionist and compassionate footing. For two decades economic and social policy in most of the world has been guided by the notion that economies function best when they are fully exposed to competitive market forces. In labour market policy, this approach is reflected in the widespread emphasis on "flexibility" - a euphemism for the retrenchment of income support and social security, the relaxation of labour market regulations, and the enhanced power of private actors to determine the terms of the employment relationship. These strategies have had marked effects on labour market outcomes, leading to greater vulnerability and polarization - and not always in ways that enhance worker-centred flexibility. The authors offer a more balanced analysis of the functioning and effects of labour market regulation and deregulation. By questioning the underpinnings of the "flexibility" paradigm, and revealing its often damaging impacts (on different countries, sectors, and constituencies), they challenge the conclusion that unregulated market forces produce optimal labour market outcomes. The authors conclude with several suggestions for how labour policy could be reformulated to promote both efficiency and equity. --Publisher's description
Keywords: Emploi; Employment (Economic theory); Labor costs; Labor demand; Labor market; Labor policy; Labor supply; Main-d'œuvre Coût; Marché du travail; Travail Politique gouvernementale; employing

Fighting for Dignity: The Ginger Goodwin Story - Stonebanks, Roger (Past CCLH Publications, 2004)
Roger Stonebanks traces the life of charismatic labour leader Ginger Goodwin from his childhood in the Yorkshire Coalfields, through his mining career in Cape Breton and British Columbia, until his untimely and controversial death in the woods of Vancouver Island. Using archival research and contemporary accounts, Stonebanks explores the historical context that surrounded Goodwin's meteoric rise in BC's labour and socialist ranks. His life, from union hall to the soccer pitch, sheds light on working-class culture in resource communities in the early years of the 20th century. Ginger Goodwin was killed while trying to evade conscription during World War I. The Military police officer responsible claimed he shot only in self-defence, but rumors have since persisted that foul play was involved in the death of the prominent socialist and labour activist. Goodwin's own words explain his opposition to conscription and war, while Stonebanks examines the background and attitude of the police officers hunting down draft dodgers. Adrian Brooks provides a legal analysis and review of the case of His Majesty the King v. Daniel Campbell and how the trial might have unfolded — if there had been a trial of Constable Campbell. Written in engaging and accessible prose, the book features several never before published photographs. --Publisher's description
Keywords: British Columbia; Draft resisters; Goodwin, Ginger; Labor Unions; Labor leaders; Officials and employees; WORLD War, 1914-1918; World War, 1914-1918

Saskatchewan: The Roots of Discontent and Protest - Warnock, John W. (Black Rose Books, 2004)
Isolation is part of the psyche of this sparsely populated prairie province, and this abundance of great open space has uniquely shaped the people, their politics, their economy and their relationship with the rest of North America. Using the broad, interdisciplinary social science approach of political economy analysis, Warnock traces Saskatchewan's past in an attempt to understand the present and glimpse some of its future. Along the way, he tells the story of Saskatchewan, from inception to centennial. --Publisher's description
Keywords: Economic conditions; Political culture; Politics and government; Social conditions

Changing Canada: Political Economy as Transformation - Clement, Wallace; Vosko, Leah F. (McGill-Queen's University Press, 2003)
Changing Canada examines political transformations, welfare state restructuring, international boundaries and contexts, the new urban experience, and creative resistance. The authors question dominant ways of thinking and promote alternative ways of understanding and explaining Canadian society and politics that encourage progressive social change. They examine how the evolution of capitalism is producing new types of transformations and new forms of resistance, and show that aspects of the state and the wider society are being contested. They also discuss the often paradoxical or contradictory effects of various social forces, such as the liberating but also constraining features of new communications technologies, new employment norms, and new household forms. --Publisher's description
Keywords: Aufsatzsammlung; Canada; Canada Conditions sociales 1991-; Canada Conditions économiques 1991-; Canada Economic conditions 1991-; Canada Politics and government 1980-; Canada Politics and government 1993-2006; Canada Politique et gouvernement 1993-2006; Canada Social conditions 1991-; Capitalisme; Changement politique; Changement social; Changement économique; Développement social Canada; Economic history; Kanada; Politics and government; Politieke ontwikkeling; Politische Ökonomie; Politischer Wandel; Science économique; Since 1980; Sociaal-economische ontwikkeling; Social change; Social change Canada; Social conditions; Sozialer Wandel; Wirtschaftsreform; État-Providence

Narratives at Work: Women, Men, Unionization, and the Fashioning of Identities - Cullum, Linda K (Social and economic studies (St. John's, NL), 2003)
In February, 1948, a group of fish and blueberry processors formed the exclusively female, Ladies' Cold Storage Workers Union at Job Brothers fish plant in St. John's, Newfoundland. Unusual for the time, this organization was founded in the context of structural and social change in the Newfoundland fishery that altered the social relations of paid and unpaid work for women fish plant labourers. Cullum carefully explores this specific labour process and provides an open reading of the workers' narratives; a study of how the women of Job Brothers recounted stories of their work and domestic lives, and thus fashioned shifting identities as gendered, classed, and racialized subjects. --Publisher's description

Trade Unions in Renewal: A Comparative Study - Fairbrother, Peter; Yates, Charlotte A. B. (Charlotte Alyce Bronwen) (Employment and work relations in context series, 2003)
This comprehensive survey of continuity and change in trade unions looks at five primarily English-speaking countries: the USA, Canada, Australia, New Zealand and the UK. The authors consider the recent re-examination by trade union movements of the basis of union organization and activity in the face of a harsher economic and political climate. One of the impetuses for this re-examination has been the recent history of unions in the USA. American models of renewal have inspired Australia, New Zealand and the UK, while Canada has undergone a cautious examination of the US model with an attempt to develop a distinctive approach. This book aims to provide a thorough grounding for informed discussion and debate about the position and place of trade unions in modern economies. --Publisher's description
Keywords: Commonwealth countries. Comparative industrial relations. Syndicats. Relations industrielles comparées. Sindicalismo. Sindicato. Comparative industrial relations. Labor unions; Labor unions. Labor unions; United States. Labor unions

Michel Chartrand : la colère du juste, 1968-2003 - Foisy, Fernand (Lanctôt, 2003)
Deuxième volet de la biographie de Michel Chartrand (Les voix d’un homme de parole), La colère du juste retrace les événements marquants de la vie du célèbre syndicaliste depuis mai 1968 jusqu’à nos jours. Ses prises de position éclatantes, ses multiples démêlées avec l’appareil judicaire, ses nombreux emprisonnements, dont sa détention lors de la crise d’Octobre 1970 (« Un jour quelqu’un va payer pour tous ces jours passés sans soleil et sans femme… »), les luttes multiples, syndicales et autres, qu’il a menées pour le mieux-être et la sécurité des travailleurs, les complots et manigances douteuses dont il a été souvent victime, avec en toile de fond une tranche importante de l’histoire du Québec moderne, tels sont les principaux éléments qui forment la trame de cette biographie imposante. Fernand Foisy a réussi à recréer le climat de l’époque, en donnant la parole aux principaux acteurs, rectifiant ici et là certaines notions erronées qui ont été véhiculées à propos de ce indomptable justicier au tempérament fougueux, Michel Chartrand. Un homme d’action et de parole, dont on découvrira tout le charme et ses passions pour la culture. Ce deuxième tome coïncide avec la diffusion de la deuxième partie de la série Simone et Chartrand, diffusée cet automne sur les ondes de Télé-Québec. --Résumé de l'éditeur
Keywords: Biographies; Chartrand, Michel; Dirigeants syndicaux Québec (Province) Biographies; History; Labor leaders; Labor leaders Québec (Province) Biography; Labor unions; Labor unions Québec (Province) History; Politics and government; Québec; Québec (Province) Conditions sociales 1960-1991; Québec (Province) Politics and government 1960-; Québec (Province) Politique et gouvernement 1960-; Since 1960; Syndicalism; Syndicalism Québec (Province); Syndicalisme Québec (Province); Syndicats Québec (Province) Histoire; Travailleurs Québec (Province) Conditions sociales; Travailleurs Québec (Province) Histoire; Working class; Working class Québec (Province) History; Working class Québec (Province) Social conditions; Working class Social conditions

L'histoire des mineurs du nord ontarien et québécois, 1886-1945 - Gaudreau, Guy; Daoust, Alain; De la Riva, Paul; Reilly, Karey (Cahiers des Amériques, 2003)
L’auteur fait revivre les itinéraires de milliers de travailleurs qui ont sillonné les mines du Nord-Est ontarien et du Nord-Ouest québécois au cours des premières décennies du xxe siècle. Grâce à l’exploitation des dossiers du personnel de sept sociétés minières réparties sur ce territoire, il scrute les arrivées et les départs des ouvriers-mineurs en cherchant à comprendre leurs motivations. L’image se dégageant de ces sources patronales reste fort différente de celle rapportée par l’histoire ouvrière et syndicale. En effet, ces travailleurs quittent d’eux-mêmes leur emploi beaucoup plus souvent qu’ils ne sont congédiés ou mis à pied, de sorte que leur chômage serait davantage volontaire qu’imposé. Étant donné la relative rareté de la main-d’œuvre spécialisée, les employeurs n’auraient pas eu d’autre choix que de réembaucher ceux qu’ils avaient auparavant engagés, et même ceux qu’ils avaient déjà congédiés. En somme, ces travailleurs, qui annoncent très souvent leur décision de « sacrer leur camp », affichent une indépendance face aux entreprises et une capacité de résistance qu’on ne soupçonnait pas. --Résumé de l'éditeur
Keywords: History; Mineral industries; Mineral industries Ontario, Northern History; Mineral industries Québec (Province) Abitibi-Témiscamingue History; Miners; Miners Ontario, Northern History; Miners Québec (Province) Abitibi-Témiscamingue History; Mineurs Québec (Province) Abitibi-Témiscamingue Histoire; Northern Ontario; Québec Abitibi-Témiscamingue

Westcountrymen in Prince Edward's Isle - Greenhill, Basil; Giffard, Ann (Formac, 2003)
This classic, first-of-its-kind study of merchant shipping illuminates the manner in which the rapid development of shipbuilding in Prince Edward Island played a significant role in Canada's early history. James Yeo, Sr., once a village labourer in his native Cornwall, came to the colony and quickly amassed a fortune from both shipbuilding and trade. His rough-and-ready business deals spawned his mercurial rise to prominence in the colony. First published in 1967, this book originated from an idea by Ann Giffard and was jointly executed with her husband, Basil Greenhill. It connects the burgeoning expansion of shipbuilding in the colonies with the settlers' hometown in Devon, and explains why, when Britain was cut off from supplies of wood in Europe, shipbuilding suddenly took hold in Canada. It is an unique study that shows that local history is an important window into the interconnected world of economic development. --Publisher's description
Keywords: Commerce; Great Britain; Great Britain Commerce Prince Edward Island; History; Prince Edward Island; Prince Edward Island Commerce Great Britain; Shipbuilding; Shipbuilding Prince Edward Island History; Shipping; Shipping Prince Edward Island History

Industrial Sunset: The Making of North America's Rust Belt, 1969-1984 - High, Steven C. (University of Toronto Press, 2003)
Plant shutdowns in Canada and the United States from 1969 to 1984 led to an ongoing and ravaging industrial decline of the Great Lakes Region. This book offers a comparative regional analysis of the economic and cultural devastation caused by the shutdowns, and provides an insightful examination of how mill and factory workers on both sides of the border made sense of their own displacement. The history of deindustrialization rendered in cultural terms reveals the importance of community and national identifications in how North Americans responded to the problem. Based on the plant shutdown stories told by over 130 industrial workers, and drawing on extensive archival and published sources, and songs and poetry from the time period covered, Steve High explores the central issues in the history and contemporary politics of plant closings. In so doing, this study poses new questions about group identification and solidarity in the face of often dramatic industrial transformation. --Publisher's description

When Coal was King: Ladysmith and the Coal-Mining Industry on Vancouver Island - Hinde, John Roderick (UBC Press, 2003)
The town of Ladysmith was one of the most important coal-mining communities on Vancouver Island during the early twentieth century. The Ladysmith miners had a reputation for radicalism and militancy and engaged in bitter struggles for union recognition and economic justice, most notably the Great Strike of 1912-14. This strike, one of the longest and most violent labour disputes in Canadian history, marked a watershed in the history of the town and the coal industry. --Publisher's description
Keywords: British Columbia Ladysmith; British Columbia Vancouver Island; Coal miners; Coal mines and mining; Coal mining History; History; Ladysmith (B.C.); Social aspects History; Social conditions History; Strikes and lockouts

From Consent to Coercion: The Assault on Trade Union Freedoms - Panitch, Leo; Swartz, Donald (Garamond Press, 2003)
Examines the "coercive assault" (i.e., legislative overrides) on trade union rights in Canada by both federal and provincial governments from the 1970s to the early 2000s. Also discusses labour-related decisions of the Supreme Court, and strategies for union renewal. Includes tables of union membership, strikes and lockouts, back-to-work measures, use of designations, and complaints of violations of union rights filed with the International Labor Organization.
Keywords: Collective bargaining; History; Labor Unions; Law and legislation

Gendered States: Women, Unemployment Insurance, and the Political Economy of the Welfare State in Canada, 1945-1997 - Porter, Ann (Studies in comparative political economy and public policy, 2003)
In the period since the Second World War there has been both a massive influx of women into the Canadian job market and substantive changes to the welfare state as early expansion gave way, by the 1970s, to a prolonged period of retrenchment and restructuring. Through a detailed historical account of the Unemployment Insurance (UI) program from 1945 to 1997, Ann Porter demonstrates how gender was central both to the construction of the post-war welfare state, as well as to its subsequent crisis and restructuring. Drawing on a wide range of sources (including archival material, UI administrative tribunal decisions, and documents from the government, labour and women's groups) she examines the implications of restructuring for women's equality, as well as how women's groups, labour and the state interacted in efforts to shape the policy agenda. Porter argues that, while the post-war welfare state model was based on a family with a single male breadwinner, the new model is one that assumes multiple family earners and encourages employability for both men and women. The result has been greater formal equality for women, but at the same time the restructuring and reduction of benefits have undermined these gains and made women's lives increasingly difficult. Using concepts from political economy, feminism, and public policy, this study will be of interest across a range of disciplines. --Publisher's description
Keywords: Economic policy; Employment; History; Social policy; Unemployment insurance; Women

Paul has a Summer Job: Graphic Novel - Rabagliati, Michel. (Drawn and Quarterly, 2003)
Rabagliati's strip "Paul: Apprentice Typographer" was one of the highlights of 1999's Drawn & Quarterly anthology, and his first comic book Paul in the Country won the 2000 Harvey award for Best New Talent. This, his first graphic novel, is eagerly anticipated by comix connoisseurs who enjoy a sweet, unsentimental story about being a teenager and Rabagliati's crisp retro-modern 1950s drawing style. This book continues the story of Paul, a Quebecois teenager in the 1970s, as he experiences the first conflicts of responsibility with his desire to be free. Paul is outraged that he is forced to stop his high school art training. But he's been asked to put art aside because his other grades are so terribly low. Defiant, he quits school and anticipates a summer of leisure. But instead Paul follows the path of so many Quebecois teenagers: he lands a job as a counselor at one of the many summer camps in the mountains outside the city. There he finds himself guiding a motley band of kids, misfits and troublemakers, much like himself. After quitting school and trying his luck in the "real world," average teenager Paul gets a job as a counselor at a summer camp run for underprivileged children in 1970s Quebec. --Publisher's description
Keywords: Blue-collar work; Camp Counsellor; Comic books, strips, etc; Factory; Montreal, Quebec; Teenager

Unions in the Time of Revolution: Government Restructuring in Alberta and Ontario - Reshef, Yonatan; Rastin, Sandra (University of Toronto Press, 2003)
The election of neo-conservative governments in Alberta and Ontario in the early 1990s brought dramatic changes to provincial public policy; both the Ralph Klein Revolution and Mike Harris' Common Sense Revolution emphasized fundamental changes in the role of government, balanced budgets, and the elimination of provincial debts. While public sector unions were forced to react, the response of the Alberta and Ontario unions differed significantly. The reasons, outcome, and long-term impact of the difference is the focus of Yonatan Reshef and Sandra Rastin's careful and revealing analysis. The authors' argument concentrates on union responses to the neo-conservative transformation in the two affected provinces, but the scope of the discussion expands to cover such issues as the differences between the two regimes, the damage to the Ontario labour movement dealt by the labour-oriented NDP government, the limits of inter-union cooperation, and the role of modern unions in politics. Lively and timely, Unions in the Time of Revolution places Canada's unions in the full context of the neo-conservative trend in provincial politics, and demonstrates the importance of individual union responses in times of such significant change. --Publisher's description. Contents: Alberta and Ontario: Industrial relations and their contexts -- Revolutions, Canada style -- Collective action conceptual framework -- Revolutionizing the Civil Service: OPSEU and AUPE -- Teachers: Protecting the profession, defending the union organization -- Sins of commission and sins of omissions: The Ontario days of action and missed opportunities in Alberta -- Sleeping with the devil: Strategic voting in the 1999 Ontario Election -- Revisiting the collective action model -- Additional thoughts on collective action.
Keywords: Alberta. Employee-management relations in government; Alberta. Government employee unions; Employee-management relations in government; Ontario. Employee-management relations in government. Government employee unions; Ontario. Fonction publique; Ontario. Fonctionnaires; Ontario. Government employee unions; Relations de travail; Syndicats

The Oriental Question: Consolidating a White Man's Province, 1914-1941 - Roy, Patricia (University of British Columbia Press, 2003)
[The author] continues her study into why British Columbians – and many Canadians from outside the province – were historically so opposed to Asian immigration. Drawing on contemporary press and government reports and individual correspondence and memoirs, Roy shows how British Columbians consolidated a “white man’s province” from 1914 to 1941 by securing a virtual end to Asian immigration and placing stringent legal restrictions on Asian competition in the major industries of lumber and fishing. While its emphasis is on political action and politicians, the book also examines the popular pressure for such practices and gives some attention to the reactions of those most affected: the province’s Chinese and Japanese residents. --Publisher's description
Keywords: 1900-1999; British Columbia; British Columbia Emigration and immigration History 20th century; British Columbia Politics and government 20th century; British Columbia Race relations; China; China Emigration and immigration History 20th century; Chinese; Chinese British Columbia History 20th century; Chinesen; Chinois Colombie-Britannique Histoire 20e siècle; Einwanderung; Emigration and immigration; Ethnische Beziehungen; History; Immigrants; Immigrants British Columbia History 20th century; Japan; Japan Emigration and immigration History 20th century; Japanese; Japanese British Columbia History 20th century; Japonais Colombie-Britannique Histoire 20e siècle; Politics and government; Race relations

Retooling the Mind Factory: Education in a Lean State - Sears, Alan (Garamond Press, 2003)
Alan Sears examines education reform in relation to a broad process of cultural and economic change. His book makes the case that education reform is one aspect of a broad-ranging neo-liberal agenda that aims to push the market deeper into every aspect of our lives by eliminating or shrinking non-market alternatives. The author begins by showing that advocates of education reform have had to make the case that the current system is not working. This sets the ground for an examination of the so-called 'Common Sense Revolution,' a claim that drastic change was required to redesign government policies to fit a changing world. Lean production methods are a crucial component of this changing world, and broader social and cultural change is now required to consolidate the emerging order built on the spread of these methods. Education reform is designed to recast the relations of citizenship, contributing to the cultural and social change promoted through the social policy of the lean state. --Publisher's description
Keywords: Conservatism; EDUCATIONAL change; Economic aspects; Education; Education and state; Ontario

Forces of Labor: Workers' Movements and Globalization since 1870 - Silver, Beverly J. (Cambridge studies in comparative politics, 2003)
Recasting labor studies in a long-term and global framework, the book draws on a major new database on world labor unrest to show how local labor movements have been related to world-scale political, economic, and social processes since the late nineteenth century. Through an in-depth empirical analysis of select global industries, the book demonstrates how the main locations of labor unrest have shifted from country to country together with shifts in the geographical location of production. It shows how the main sites of labor unrest have shifted over time together with the rise or decline of new leading sectors of capitalist development and demonstrates that labor movements have been deeply embedded (as both cause and effect) in world political dynamics. Over the history of the modern labor movement, the book isolates what is truly novel about the contemporary global crisis of labor movements. Arguing against the view that this is a terminal crisis, the book concludes by exploring the likely forms that emergent labor movements will take in the twenty-first century. --Publisher's description. Contents: Introduction -- Labor movements and capital mobility -- Labor movements and product cycles -- Labor movements and world politics -- Contemporary dynamics in world-historical perspective -- Appendix A: The World Labor Group Database: conceptualization, measurement, and data collection procedures -- Appendix B: Instructions for recording data from indexes -- Appendix C: Country classifications.
Keywords: Automobile industry workers; Business relocation; Capitalism; Economic aspects History; Globalization; History; Labor disputes; Labor movement; Manufacturing processes; TEXTILE workers

Walking the Union Walk: Stories From the Communications, Energy, and Paperworkers Union - Swift, Jamie (Between the Lines, 2003)
Hi-tech tactics during a strike at a dockside factory in Montreal. A workplace cancer tragedy in Sarnia, Ontario. Immigrant workers sticking with their union at the chocolate factory. A struggle for pay equity in the courts and on the streets. A campaign to create jobs by cutting hours of work in B.C. An organizing drive 350 kilometres out into the frigid Atlantic. These are some of the fascinating stories told by Jamie Swift in his chronicle of the first ten eventful years of one of the most dynamic labour unions in North America. --Publisher's description
Keywords: Communication, Energy and Paperworkers Union of Canada; Employees; Energy industries; History; Labor Unions; Paper industry workers; Telecommunication

All Hell Can't Stop Us: The On-to-Ottawa Trek and Regina Riot - Waiser, W. A. (Bill) (Fifth House Books, 2003)
In early June 1935, one thousand relief-camp strikers clambered aboard freight trains to take their grievances to Ottawa. Their trek would end in bloodshed on the streets of Regina on 1 July 1935, later known as "The bloodiest day of the Depression." In All Hell Can't Stop Us, noted historian Bill Waiser examines the social and political background of the On-to-Ottawa Trek and Regina Riot, and provides an in-depth account of the strikers, their supporters, and their powerful adversaries. This gripping history includes many unpublished sketches and photographs. --Publisher's description
Keywords: Unemployed -- Canada -- History -- 20th century

Naming the System: Inequality and Work in the Global Economy - Yates, Michael D. (Monthly Review Press, 2003)
The economic boom of the 1990s created huge wealth for the bosses, but benefited workers hardly at all. At the same time, the bosses were able to take the political initiative and even the moral high ground, while workers were often divided against each other. This new book by leading labor analyst Michael D. Yates seeks to explain how this happened, and what can be done about it. Essential to both tasks is "naming the system"-the system that ensures that those who do the work do not benefit from the wealth they produce. Yates draws on recent data to show that the growing inequality - globally, and within the United States - is a necessary consequence of capitalism, and not an unfortunate side-effect that can be remedied by technical measures. To defend working people against ongoing attacks-on their working conditions, their living standards, and their future and that of their children-and to challenge inequality, it is necessary to understand capitalism as a system and for labor to challenge the political dominance of capitalist interests. Naming the System examines contemporary trends in employment and unemployment, in hours of work, and in the nature of jobs. It shows how working life is being reconfigured today, and how the effects of this are masked by mainstream economic theories. It uses numerous concrete examples to relate larger theoretical issues to everyday experience of the present-day economy. And it sets out the strategic options for organized labor in the current political context, in which the U.S.-led war on terrorism threatens to eclipse the anti-globalization movement. --Publisher's description.
Keywords: ANTI-globalization movement; Capitalism; Globalization; Income distribution; Industrial relations; Labor; Labor movement; QUALITY of work life; Unemployment

Tortillas and Tomatoes: Transmigrant Mexican Harvesters in Canada - Basok, Tanya (McGill-Queen's studies in ethnic history, 2002)
An exploration of the vital role played by Mexican seasonal workers in Canadian agriculture and how they have become a structural necessity in some sectors. Based on interviews with Leamington greenhouse growers and migrant Mexican workers, Tanya Basok offers a timely analysis of why the Seasonal Agricultural Workers Program is needed. She argues that while Mexican workers do not necessarily constitute cheap labour for Canadian growers, they are vital for the survival of some agricultural sectors because they are always available for work, even on holidays and weekends, or when exhausted, sick, or injured. Basok exposes the mechanisms that make Mexican seasonal workers unfree and shows that the workers' virtual inability to refuse the employer's demand for their labour is related not only to economic need but to the rigid control exercised by the Mexican Ministry of Labour and Social Planning and Canadian growers over workers' participation in the Canadian guest worker program, as well as the paternalistic relationship between the Mexican harvesters and their Canadian employers. --Publisher's description
Keywords: Foreign workers, Mexican; Ontario. Agricultural laborers, Foreign; Ontario. Agricultural laborers, Foreign. Foreign workers, Mexican; Ontario. Trabajadores extranjeros mexicanos; Ontario. Travailleurs agricoles étrangers; Ontario. Travailleurs étrangers mexicains

Colonization and Community: The Vancouver Island Coalfield and the Making of the British Columbian Working Class - Belshaw, John Douglas (McGill-Queen's University Press, 2002)
An examination of the social, political, and demographic history of British miners and their households on Vancouver Island in the nineteenth century. In the nineteenth century coal-miners imported from Europe, Asia, and eastern North America burrowed beneath the Vancouver Island towns of Nanaimo, Wellington, and Cumberland. No group was as numerous and influential in this enterprise as the hundreds of British immigrants who traveled half-way around the world to take up back-breaking work in the most remote colony in the Empire. What drew the British miners and their families to the north Pacific? Why did they set aside six months to journey to a colony about which they knew little? Once they reached Vancouver Island, what did they make of it and what did they make it into? And how did they re-make themselves in the process? In Colonization and Community John Belshaw takes a new look at British Columbia's first working class, the men, women, and children beneath and beyond the pit-head. Beginning with an exploration of emigrant expectations and ambitions, he investigates working conditions, household wages, racism, industrial organization, gender, schooling, leisure, community building, and the fluid identity of the British mining colony, the archetypal west coast proletariat. By connecting the story of Vancouver Island to the larger story of Victorian industrialization, he delineates what was distinctive and what was common about the lot of the settler society. Belshaw breaks new ground, challenging the easy assumptions of transferred British political traditions, analyzing the colonial at the household level, and revealing the emergent communities of Vancouver Island as the cradle of British Columbian working-class culture. --Publisher's description

Labour Law in Canada - Carter, Donald D.; England, Geoffrey; Etherington, Brian; Trudeau, Gilles (Wolters Kluwer, 2002)
For a clear understanding of the legal protections and remedies available to employers and workers in Canada, this convenient survey and analysis is ideal. Although it may be said that there are eleven distinct systems of labour law in Canada - encompassing ten provinces and the Federal government - the authors ensure depth of treatment by focusing on common policy themes and typical legal solutions, with significant departures noted in whatever province or area of law they may arise. However, the relevant law of the three most populous and influential provinces - Quebec, Ontario, and British Columbia - is covered in particular detail, as is Federal labour legislation and case law. Among the important areas of Canadian law and practice emphasised are the following: the tension between trade union power and business flexibility; collective "labour law" and individual "employment law"; the effect of the North American Free Trade Agreement; the central place of the legal concept of the employment contract; labour standards legislation; the influence of the 1982 Charter of Rights and Freedoms; court intervention in labour law, both under common law principles and Quebec's civil code; the role of labour relations boards; and judicial review of administrative decisions and arbitration awards. As an accurate and usable guide for lawyers not expert in Canadian law, Labour Law in Canada is without peer. --Publisher's description
Keywords: Bargaining; Collective Agreements; Labour Movement; Labour law; Trades; Unions

Bienfait: The Saskatchewan Miners' Struggle of '31 - Endicott, Stephen Lyon (University of Toronto Press, 2002)
Against all odds, the miners of Bienfait, Saskatchewan, attempted, in 1931, to change their miserable situation by organizing a union. Exploring the social consequences of capitalist restructuring during the Great Depression, Stephen Endicott focuses on the miners' tumultuous thirty-day strike. Their bid to gain union recognition with the aid of the Workers' Unity League of Canada ultimately failed, and Endicott's in-depth examination of the key factors and players attempts to explain why this was the case and why a similar union drive a decade later succeeded." "Based on a large number of both oral and written primary resources, Bienfait offers a new interpretation of the role of corporations, governments, courts, and the police in the events surrounding the strike. In the process, Endicott demonstrates how a militant union leadership helped the workers gain the strength and unity of purpose to challenge the powers of wealth and deep-seated prejudice. Bienfait opens a new chapter in the history of Canadian labour relations that reveals much about Canadian and Canadian society during the Depression. --Publisher's description
Keywords: Coal Miners' Strike, Estevan, Sask., 1931.; Grève des mineurs de charbon, Estevan, Sask., 1931

Cabbagetown: The Classic Novel of the Depression in Canada - Garner, Hugh (McGraw-Hill Ryerson, 2002)
Toronto's Cabbagetown in the Depression...North America's largest Anglo-Saxon slum. Ken Tilling leaves school to face the bleak prospects of the dirty thirties-where do you go, what do you do, how do you make a life for yourself when all the world offers in unemployment, poverty and uncertainty?"As a social document, Cabbagetown is as important and revealing as either The Tin Flute or The Grapes of Wrath. Stern realism has also projected upon the pages of a whole gallery of types, lifelike and convincing. He is well fitted to hold the mirror up to human nature." Globe and Mail.Cabbagetown was first published in an abbreviated paperback edition in 1950 and was published in its entirety in 1968. This, the first quality paperback edition, contains the full unexpurgated text of Cabbagetown. --Publisher's description
Keywords: Poor; Poverty; Slums; Social Class and Equality; Toronto (Ont.); Unemployment

Their Own History: Women's Contribution to the Labour Movement of British Columbia - Griffin, Betty; Lockhart, Susan (United Fishermen & Allied Workers Union/CAW Seniors Club, 2002)
The United Nations declared 1975 International Women's Year for the purpose of promoting equality of men and women.... Canada alloted funds for projects aimed at achieving these objectives and many projects were undertaken across the country. The Central Council of Women's Auxiliaries to the United Fishermen & Allied Workers' Union at its annual convention in 1975 undertook to write a history highlighting women's contribution to the trade union movement in British Columbia. Finally, here is that book. Working people in BC have a proud history: a history that accalims the struggles for a better life, a better job and a better community. In 1975, we set out to record the history of the women of British Columbia who struggled for human rights and women's equality and who helped build our trade unions. We interviewed and recorded a wonderful group of women and men. And we appreciated all their stories. [This book] shares those stories. --Publisher's description
Keywords: Biographies; British Columbia; Femmes Travail Colombie-Britannique Histoire; Femmes dans le mouvement ouvrier Colombie-Britannique Histoire; History; Personnel féminin Colombie-Britannique Biographies; Women Employment; Women Employment British Columbia History; Women employees; Women employees British Columbia Biography; Women in the labor movement; Women in the labor movement British Columbia History

Is Anyone Listening?: Women, Work, and Society - Jacobs, Merle; Armstrong, Pat; Armstrong, Hugh; Bannerji, Himani; Hagey, Rebecca; MacKay, Robert W.; Ng, Roxana; Gupta, Tania Das; George, Usha; Bruckert, Chris; Kirk, Jo-Anne; Daenzer, Patricia; et al. (Women's Press, 2002)
Jacobs has brought together the work of a number of progressive feminist writers, who theorize gender, race, diversity research, the social construction of women and work, ethnicity and class. The essays in this reader are focused on issues relating to gender equality in workspaces in society. The editor has gathered essays from well-known and established social scientists. Among them are Pat and Hugh Armstrong, Himani Bannerji, Christine Bruckert and Tania Das Gupta. The result is a stimulating collection that focuses on health-care workers, teachers, strippers, wage-less workers and women who are hidden from view. The collection explores the construction of gender, the selection of careers and the differential in work conditions and wages. --Publisher's description. Contents: Theorizing women's work: feminist methodology / Pat Armstrong and Hugh Armstrong -- The paradox of diversity: the construction of a multicultural Canada and "women of colour" / Himani Bannerji -- Qualitative research to identify racialist discourse: towards equity in nursing curricula / Rebecca Hagey and Robert W. MacKay -- Teaching against the grain: contradictions and possibilities / Roxana Ng -- Racism in nursing / Tania Das Gupta -- Toward anti-racism in social work in the Canadian context / Usha George -- The world of the professional stripper / Chris Bruckert -- Gender inequality and medical education / Jo-Anne Kirk -- Benevolent patriarchy: the foreign domestic movement, 1980-1990 / Patricia Daenzer -- The new wageless worker: volunteering and market-guided health care reform / Elizabeth Esteves -- "Who else would do it?": female family caregivers in Canada / Kristin Blakely -- Marginal women: examining the barriers of age, race and ethnicity / Robynne Beugebauer -- Creating understanding from research: staff nurses' views on collegiality / Merle Jacobs -- Antiracism advocacy in the climate of corporatization / Rebecca Hagey, Jane Turrittin, Evelyn Brody -- Undertaking advocacy / Merle Jacobs.

Harnessing Labour Confrontation: Shaping the Postwar Settlement in Canada, 1943-1950 - McInnis, Peter S. (Peter Stuart) (University of Toronto Press, 2002)
The 1940s in Canada are crucial to the understanding of labour history in this country. Following the Depression, and sparked by the need to mobilize the workforce during the Second World War, this decade led to a restructuring of the relationship between labour and the state. In Harnessing Labour Confrontation, Peter S. McInnis examines the reformation of Canadian society and its industrial relations regime from the perspective of labour organizations and their supporters and from that of government and business. What results is a synthesis of labour and political history, which the author uses to analyze in a North American context the role of confrontation and heated debate in the formation of a national postwar compromise and in the birth of a modern welfare state.Among the factors affecting the postwar compromises were, argues McInnis, the divided jurisdiction between federal and provincial governments, the return to gender-biased societal norms, a developing Cold War climate of national insecurity, and a promise of strong consumer purchasing power based on postwar wages and benefits packages. While some of the results of the 1940s compromise and the welfare state remains intact today, many of the political and social structures have deteriorated in the last two decades. --Publisher's description

Cows Don't Know It's Sunday: Farming in St. John's - Murray, Hilda Chaulk (Social and economic studies (St. John's, NL), 2002)
Before 1950, the greatest number of Newfoundland farmers lived in the St. John's area. They and the townsfolk were interdependent, with the farmers providing meat, poultry, garden and dairy products to the city, while St. John's served as a ready market and a source of cash income. Although many street names serve as reminders of those who once worked the land, and others perpetuate old homesteads, the farmers of St. John's are as unknown today as though they had never been. Cows Don't Know It's Sunday gives a historical overview of farming and its importance to the economy of Newfoundland, and describes in detail, using the words of more than eighty people who grew up on or near farms, what it was like to farm in and around St. John's in the period within living memory. Farmers worked seven days a week throughout the year. This study of both the work life and social life of the farmers of St. John's is a tribute to the farming families who were the mainstay of the city during the first half of the twentieth century. --Publisher's description

The Contested Past: Reading Canada's History: Selections from the Canadian Historical Review - Shore, Marlene (University of Toronto Press, 2002)
This collection of selected excerpts focuses on the Canadian Historical Review's contribution to the study of Canadian history from the journal's founding in 1920 to the present. Using the CHR's own interconnected objectives as a benchmark - the promotion of high standards of historical research and writing in Canada, and the fostering of the study of Canadian history - Marlene Shore analyses the varying degrees of success the journals had in meeting its those goals. Her introductory essay shows how the CHR was shaped not only by its own editorial policies, but by international currents affecting the discipline of history and its practitioners. The excerpts, each accompanied by critical commentary, were chosen as representative of the major trends, crucial studies, and main controversies in Canadian historical writing. Shore has arranged them chronologically and thematically into four sections: Nation and Diversity, 1920-1939; War, Centralization, and Reaction, 1940-1965; The Renewal of Diversity, 1966 to the Present; and Reflections. Among the key themes explored by Shore and the contributing historians, Native-European contact, society and war, the nature of Canadian and Quebec nationalism, class-consciousness, and gender politics are highlighted. Broad in scope and focused in intent, The Contested Past offers an excellent introduction to twentieth century Canadian history and historiography. --Publisher's description
Keywords: Canada -- Historiography

Contingent Work, Disrupted Lives: Labour and Community in the New Rural Economy - Winson, Anthony; Leach, Belinda (Studies in comparative political economy and public policy, 2002)
[E]xamines the effects of economic globalization on several manufacturing-dependent rural communities in Canada. In looking at such contemporary corporate strategies as plant closures and downsizing, authors [The authors] consider the impact of capitalist restructuring on the residents of various communities. [They] argue that the new rural economy has caused considerable instability and hardship in the lives of rural residents as they struggle to adapt in the face of economic upheaval."--Publisher's description. Contents: The Global and the Local: Understanding Globalization through Community Research -- Community Sketches, History, and Method -- The New Rural Economy and the Shape of Restructuring -- Skidding into the Contingent Work World -- 'Forget All Your Dreams and Good Luck with Your Life': Lay-Off and the New Reality of Contingent Labour -- Economic Diversity, Sustainability, and Manufacturing Communities. Geographic: Ontario. Ontario. Includes bibliographical references (pages 205-220) and index.
Keywords: Aspect social; Ontario. Chômage en milieu rural; Ontario. Deindustrialization; Ontario. Deindustrialization. Displaced workers. Globalization; Ontario. Desempleo; Ontario. Displaced workers; Ontario. Désindustrialisation; Ontario. Globalization; Ontario. Industrie rurale; Ontario. Mondialisation; Ontario. Rural industries; Ontario. Trabajadores; Ontario. Travailleurs; Ontario. Travailleurs licenciés; Ontario. Working class; Rural unemployment; Social aspects; Social aspects. Rural industries. Rural unemployment. Working class. Landwirtschaft. Arbeitslosigkeit

Mirrors of Stone: Fragments from the Porcupine Frontier - Angus, Charlie; Palu, Louie (Between the Lines, 2001)
Mirrors of Stone delves into the many ethnic cultures that thrived in the mining areas of Northern Ontario from the 1920s to the 1960s. The stormy history of hardrock mining camps has never fit into the comfortable cliches by which Canada “tells its story.” Angus unearths the dark sides of this history–“the wild tales of bootleggers, mobsters, and prostitution rings” and in so doing opens up new ways of seeing Ontario’s history and culture. --Publisher's description

Building a Better World: An Introduction to Trade Unionism in Canada - Black, Errol; Silver, Jim (Fernwood, 2001)
This introductory text examines the vital role of trade unions in Canada. In particular, it emphasizes how the values. objectives and activities of unions are shaped and changed in the context of employer opposition and often hostile governments. --Publisher's description.
Keywords: Labor unions -- Canada

Framing Our Past: Canadian Women's History in the Twentieth Century - Cook, Sharon Anne; McLean, Lorna; O'Rourke, Kate (McGill-Queen's University Press, 2001)
Framing Our Past is about women's lived experience. Drawing from diaries, oral history, letters, organizational records, paintings, quilts, dressmaking patterns, milliners' records, and posters, the contributors offer fresh interpretations of this historical material and unique insights into the lives of individual Canadian women who expanded the boundaries of traditional roles. Lavishly illustrated, Framing Our Past looks at women and their social rituals with other women, organized sporting clubs, philanthropic, spiritual and aesthetic activities, study and reading groups. The authors explore women's roles as nurturers and keepers of the hearth and in family management, child care, and health care. They highlight women's work in areas as diverse as domestic labour, nursing, dressmaking, broadcasting, and banking as well as women's contributions to education and their instrumental political role in consumer activism, social work, and peace movements. --Publisher's description
Keywords: Women -- Canada -- History -- 20th century

La pensée de Gustave Francq, syndicaliste et réformateur social : textes choisis, 1905-1948 - Francq, Gustave; Leroux, Éric (Collection RCHTQ, 2001)
Keywords: 1900-1999; Canada; Francq, Gustave, 1871-1952 Pensée politique et sociale; Francq, Gustave, Political and social view; History; Labor unions; Labor unions Canada History 20th century; Québec; Québec (Province) Conditions sociales 20e siècle; Québec (Province) Social conditions 20th century; Social conditions; Syndicalism; Syndicalism Québec (Province) History; Syndicalisme Québec (Province) Histoire; Syndicats Canada Histoire 20e siècle

Labour Before the Law: The Regulation of Workers' Collective Action in Canada, 1900-1948 - Fudge, Judy; Tucker, Eric (Canadian social history series, 2001)
In this study of the relations between workers and the state, Judy Fudge and Eric Tucker examine the legal regulation of workers' collective action from 1900 to 1948. They analyze the strikes, violent confrontations, lockouts, union organizing drives, legislative initiatives, and major judicial decisions that transformed the labour relations regime of liberal voluntarism, which prevailed in the later part of the nineteenth century, into industrial voluntarism, whose centrepiece was Mackenzie King's Industrial Disputes Investigation Act of 1907. This period was marked by coercion and compromise, as workers organized and fought to extend their rights against the profit-oriented owners of capital, while the state struggled to define a labour regime that contained industrial conflict. The authors then trace the conflicts that eventually produced the industrial pluralism that Canadians have known in more recent years." "The book is simultaneously & history of law, aspects of the state, trade unions and labouring people, and their interaction within the broad and shifting terrain of political economy. The authors are attentive to regional differences and sectoral divergences, and they attempt to address the fragmentation of class experience. -- Publisher's description
Keywords: 20e siecle. Travail; 20th century. Syndicats; Canada; Droit; Histoire; History; Labor Unions; Law and legislation

A Very Red Life: The Story of Bill Walsh - Gonick, Cy (Past CCLH Publications, 2001)
Montreal-born Moishe Wolofsky was a nineteen year-old unemployed university drop-out in 1930 when he and his friend Dick Steele took a job aboard an ocean vessel, beginning a journey that would change his life forever. Out of money, they stumbled into Russia and took jobs in a tractor factory. There, they became dedicated communists. Dragged back to Canada by his father, the well-known Jewish publisher, Herschel Wolofsky, he soon began a career as an organizer for the Communist Party of Canada. By then Moishe Wolofsky had become Bill Walsh. Still a very young man, he led the drive to organize the rubber workers in Kitchener and subsequently the auto workers in Windsor. Jailed and interned along with several hundred other Communists, upon his release Walsh fought overseas in Holland and Belgium. After the war he took a staff position with the United Electrical Workers in Hamilton, a job he retained for over two decades. After years of conflict with UE President C.S. Jackson, Walsh was forced to quit his job and subsequently the Communist Party. In the late 60s, he began a new career in labour arbitration. This is the story of how a young idealist became a Red and helped build industrial unionism in Canada. But it is also a story of romance and adventure. Walsh actively participated in many of the 20th century's historic events. Everything he did was touched with an intensity. He was a brilliant strategist and an extraordinary teacher. Because he never held high office either in politics, in uniform, or in any of the unions he was associated with, his contributions have gone unheralded. This book provides an inside, bottom-up look at some of the most important episodes in our trade union history as well as an insight into the functioning of a venerable communist-led union. --Publisher's description
Keywords: Arbitrators, Industrial; Communist Party of Canada; Labor leaders; Political activists; United Electrical, Radio and Machine Workers of America; Walsh, Bill, 1910-2004

Gustave Francq : figure marquante du syndicalisme et précurseur de la FTQ - Leroux, Eric (VLB, 2001)
Intellectuel du mouvement ouvrier, Gustave Francq (1871-1952) a suivi une carrière hors de l’ordinaire. Il a occupé une place dans les hautes sphères décisionnelles du mouvement syndical nord-américain pendant plus de quarante ans. Sa contribution à la mise sur pied de la Fédération provinciale du travail du Québec fait de lui un précurseur de la Fédération des travailleurs et des travailleuses du Québec (FTQ). À ce sujet, soulignons qu’il est le fondateur du journal Le Monde ouvrier, aujourd’hui l’organe officiel de la FTQ. --Résumé de l'éditeur
Keywords: Francq, Gustave, 1871-1952

Getting By in Hard Times: Gendered Labour at Home and on the Job - Luxton, Meg; Corman, June Shirley (University of Toronto Press, 2001)
[D]escribes the experiences of daily life for predominantly white, working class women and men during the period of "economic restructuring" begun in the 1980s. Luxton and Corman show how the shift from a pattern where women were full-time housewives and men were income earners, to one where women are increasingly income earners as well, is altering the experience of everyday life Based on a case study conducted from 1980 to 1996, of households where one person was employed at Stelco's manufacturing plant in Hamilton, Ontario, the book examines how working class families make a living by combining paid employment and unpaid domestic labour. During this period of government cutbacks the loss of secure employment for men (as the steel plant cut its labour force by about two-thirds), combined with women's increasing participation in the labour force, resulted in lower standards of living, reduced income, and the imposition of more unpaid work on family households. [The book] examines how growing insecurities undermined class politics while increasing gender, racial, and ethnic tensions. By focusing on the daily coping strategies of white working class women and men, the book shows the human face of changing gender, race, and class politics in Canada. --Publisher's description.
Keywords: Attitudes; Case studies; Class consciousness; Hamilton, Ontario; Iron and steel workers; Sex role; Working class

Remember Kirkland Lake: The Gold Miners' Strike of 1941-42 - MacDowell, Laurel Sefton (Canadian Scholars' Press, 2001)
[This book] tells the story of one of the most important industrial disputes in Canadian labour history. This strike united the Canadian labour movement around the demand for collective bargaining legislation, which it won in 1944 and which remains central to our industrial relations system. The book provides a comprehensive analysis of all the factors in this dramatic dispute. At the community level, a social history approach examines the local living and working conditions of the miners and their families, the role of the women in the dispute, and the ethnic makeup of the workforce. -- Publisher's description
Keywords: Canada; Gold Miners' Strike, Kirkland Lake, Ont., 1941-1942. Collective bargaining; History; Mining industry

Renegade Lawyer: The Life of J.l. Cohen - MacDowell, Laurel Sefton (Published for the Osgoode Society for Canadian Legal History by University of Toronto Press, 2001)
J.L. Cohen, one of the first specialists in labour law and an architect of the Canadian industrial relations system, was a formidable advocate in the 1930s and 1940s on behalf of working people. A 'radical lawyer' in the tradition of the great American counsel Clarence Darrow or contemporary advocate Thomas Berger who represent the less powerful and seek to reform society and to protect civil liberties, Cohen was also a 'labour intellectual' in Canada, similar to those supporting Roosevelt's New Deal in the United States. He wrote Collective Bargaining in Canada, served on the National War Labour Board, and advised the Ontario government about policy issues such as mothers' allowances, unemployment insurance legislation, and labour law..

Beyond Service: State Workers, Public Policy, and the Prospects for Democratic Administration - McElligott, Greg (Institute of Public Administration of Canada series in public management and governance, 2001)
This study concerns one department of Canadian government - Employment and Immigration Canada (EIC) - and one policy field - labour market policy - from 1976 to 1991. McElligott unearths resistance in workplaces where 'cutting edge' neoconservative managers have been trying to reshape government services, and inserts front-line workers into state theories, policy debates, and progressive political strategies. He argues that the neglect of these workers makes key state theories incomplete and separates policy-making theory - and practice - from actual state outputs. One consequence is that progressive thinkers and activists have forgone many promising strategic opportunities." "Beyond Service challenges current trends in administrative theory and policy-making, and will be of interest to academics, policy research bodies, union researchers, educators, and, most important, front-line government workers themselves. --Publisher's description
Keywords: Angestellter; Canada; Canada. Emploi et immigration Canada (Ministère) Fonctionnaires Cas, Études de; Canada. Employment and Immigration Canada (Department); Canada. Employment and Immigration Canada (Department) Officials and employees Case studies; Case studies; Civil service; Civil service Canada; Employee-management relations in government; Employee-management relations in government Canada; Employees; Fonction publique Canada; Fonction publique Relations de travail Canada; Kanada Government; Management Employee participation; Management Employee participation Canada; Personalpolitik; Personnel Participation à la gestion Canada; Verwaltung; Études de cas

The Tyranny of Work: Alienation and the Labour Process - Rinehart, James W. (Harcourt Canada, 2001)
The Tyranny of Work examines the institution of work from the perspective of alienated labour, a perspective that many conventional approaches to the subject have ignored or misrepresented. Completely updated to reflect current trends in the labour force and research in the field of labour studies, The Tyranny of Work begins with a thorough discussion of work as a social problem and the sources of alienation. The book then examines the development of industrial capitalism in Canada, the white-collar and blue-collar worlds, and, finally, solutions to the problem of alienated labour. All statistics and data have been updated to reflect the most current research. Information from the 2001 Census has been integrated throughout the text. The Tyranny of Work examines the institution of work from the perspective of alienated labour, a perspective that many conventional approaches to the subject have ignored or misrepresented. --Publisher's description, 5th edition (2005).Contents: 1. Work as a social problem -- 2. Alienation and its sources -- 3. Alienation and the development of industrial capitalism in Canada -- 4. Post-industrial society and white-collar worlds -- 5. Blue-collar crime -- 6. Restructuring organizations and work -- 7. Solutions to alienated labour. Includes bibliographical references (pages 218-245) and index;
Keywords: Labor -- Canada

Montmorency : histoire d'une communauté ouvrière - Simard, Jean-François (Septentrion, 2001)
Voici une fresque émouvante de la vie des gens attachants qui ont fait au fil des siècles l’histoire touchante de cette petite ville dont le site naturel du " Sault de Montmorency ", comme l’avait baptisé Champlain, est connu de tous. Le syndicaliste Fernand Daoust, qui rédige la préface de cet ouvrage, n’hésite pas à affirmer que " Jean-François Simard, par un remarquable travail de recherche minutieuse et parfois inédite, brosse un saisissant tableau d’une petite société qui souffre, qui peine mais qui rêve aussi tout au long de ses inépuisables générations […] ". Ballottés du monde rural au monde industriel puis postindustriel, les gens de Montmorency ont développé une conscience sociale qui a marqué la lutte des travailleurs québécois. En rappelant les péripéties de ces bouleversements, Jean-François Simard nous convie à un devoir de mémoire, d’attachement et de reconnaissance envers un petit coin attachant du Québec dont le labeur et le sens des responsabilités de ses habitants ont contribué à forger l’identité d’un peuple et à perpétuer ses valeurs d’endurance et de solidarité. L’histoire des femmes et des hommes qui ont vécu à Montmorency fait partie de notre patrimoine collectif et appartient à tout le Québec. Cet ouvrage s’intéresse donc à l’essor puis au déclin d’une petite communauté ouvrière, patrie de Fernand Dumont qui s’en est grandement inspiré pour ses travaux. Cette communauté, dans sa relation au double mouvement d’industrialisation et de désindustrialisation qui a rythmé l’avènement du capitalisme au cours du dernier siècle, a marqué de manière indélébile la quête des ouvriers québécois pour une plus grande justice sociale. --Résumé de l'éditeur
Keywords: Classe ouvrière; Condition sociale; Condition économique; Développement économique régional; Histoire; History; Industrie Québec (Province) Montmorency (Beauport) Histoire; Industries; Industries Québec (Province) Montmorency (Beauport) History; Montmorency (Beauport, Québec); Montmorency (Beauport, Québec) Conditions sociales; Montmorency (Beauport, Québec) Histoire; Montmorency (Beauport, Québec) History; Montmorency (Beauport, Québec) Social conditions; Ouvrier; Québec (Canada; province) Conditions sociales; Social conditions; Sociologie rurale; Syndicalism; Syndicalism Québec (Province) Montmorency (Beauport) History; Syndicalisme Québec (Province) Montmorency (Beauport) Histoire; Travail

Public-Sector Labour Relations in an Era of Restraint and Restructuring - Swimmer, Gene; Rose, Joseph B.; Wagar, Terry H.; Philips, Paul; Stecher, Carolina; Reshef, Yonatan; Thompson, Mark; Bach, Sandra; Adams, Roy J. (Oxford University Press, 2001)
The 1990s in Canada will probably go down as the most stressful decade for public-sector industrial relations since the inception, 25 years earlier, of collective bargaining in the public service. Government debt and defecits became the rationale for downsizing, outsourcing, privatization, layoffs, buyouts, and early retirement packages at both the federal and provincial levels. When workers' bargaining units did not bend to government demands at the negotating table, and when leaders did not blink at the threat of restrictive legislation, then governments of both the right and the left at times found it convenient to legislate rule changes to suit their fiscal or ideological purposes. The contributors to Public-Sector Labour Relations examine in depth the events of recent years in the public service of six jurisdictions―Nova Scotia, Ontario, Manitoba, Alberta, British Columbia, and the federal government. Trends in the other five Canadian provinces are also considered. Only in BC has there been an essentially co-operative labour relations environment, although even in this province, public service employment has dropped considerably. Overall, from 1991 to 1997, provincial civil service employment fell by 15 per cent, while the federal employment reduction was 14 per cent. (From the employment peak in 1993-4, the overall provincial reduction was over 22 per cent.) Although collective bargaining is still alive, a major conclusion of this study is that collective bargaining in the Canadian public sector is not well. The cases reported here demonstrate that governments have adopted the attitude and policy that they may engage in bargaining or suspend it whenever they find that course of action to be convenient. Viewed from a broader international context, as discussed in the concluding chapter, the casual suspension of bargaining by Canadian governments cannot be justified by the norms and agreements that Canada has shared with the international community. -- Publisher's description. Contents: Public-sector labour relations in an era of restraint and restructuring: an overview / Gene Swimmer -- Provincial government restructuring in Nova Scotia: the freezing and thawing of labour relations / Terry H. Wagar -- From softball to hardball: the transition in labour-management relations in the Ontario public service / Joseph B. Rose -- Fiscal restraint, legislated concessions, and labour relations in the Manitoba civil service, 1988-1997 / Paul Phillips and Carolina Stecher -- The logic of union quiescence: the Alberta case / Yonatan Reshef -- Labour relations in the BC public service: blowing in the political wind / Mark Thompson -- Restructuring federal public-sector human resources / Gene Swimmer and Sandra Bach -- Public-employee relations: Canadian developments in perspective / Roy J. Adams.

Union Learning: Canadian Labour Education in the Twentieth Century - Taylor, Jeffery M. (Thompson Educational, 2001)
Over 100,000 Canadian workers participate annually in educational programs conducted by their union or the broader labour organizations to which their union belongs. Union-based education is the most significant nonvocational education available to working people. This activity has been going on for decades, and Jeffery Taylor's Union Learning: Canadian Labour Education in the Twentieth Century is the first comprehensive history of it. Union Learning chronicles the rise and decline of the Workers' Educational Association, the development of internal union educational programs, the consolidation of the Canadian Labour Congress's educational system after 1956, the origin and growth of the Labour College of Canada, and the patchy history of university and college involvement in labour education. Taylor argues that a new emphasis on broad-based and activist education today promises to rekindle the sense of an educational movement that was present in the labour movement in the 1930s and 1940s. The book includes a number of illustrative sidebars and photographs. --Publisher's description
Keywords: 20th century; Canada; Education History; History; Labor unions and education; Working class

A Fishery for Modern Times: The State and the Industrialization of the Newfoundland Fishery, 1934-1968 - Wright, Miriam (Canadian social history series, 2001)
In the early 1990s, the northern cod populations off the coast of Newfoundland had become so depleted that the federal government placed a moratorium on commercial fishing. The impact was devastating, both for Newfoundland's economy and for local fishing communities. Today, although this natural resource exploited commercially for over 500 years appears to be returning in diminished numbers, many fisheries scientists and fishers question whether the cod will ever return to its former abundance. In A Fishery for Modern Times, Miriam Wright argues that the recent troubles in the fishery can be more fully understood by examining the rise of the industrial fishery in the mid-twentieth century. The introduction of new harvesting technologies and the emergence of 'quick freezing', in the late 1930s, eventually supplanted household production by Newfoundland's fishing families. While the new technologies increased the amount of fish caught in the northwest Atlantic, Wright argues that the state played a critical role in fostering and financing the industrial frozen fish sector. Many bureaucrats and politicians, including Newfoundland's premier, Joseph Smallwood, believed that making the Newfoundland fishery 'modern', with centralization, technology, and expertise, would transform rural society, solving deep-seated economic and social problems. A Fishery for Modern Times examines the ways in which the state, ideologies of development, and political, economic, and social factors, along with political actors and fishing company owners, contributed to the expansion of the industrial fishery from the 1930s through the 1960s. While the promised prosperity never fully materialized, the continuing reliance on approaches favouring high-tech, big capital solutions put increasing pressure on cod populations in the years that followed. As Wright concludes, 'We can no longer afford to view the fisheries resources as 'property' of the state and industry, to do with it as they choose. That path had led only to devastation of the resource, economic instability, and great social upheaval." --Publisher's description

Ringing in the Common Love of Good: The United Farmers of Ontario in Lambton, Simcoe and Lanark Counties, 1914-1926 - Badgley, Kerry (McGill-Queen's University Press, 2000)
Founded in 1914, the United Farmers of Ontario (UFO) became a significant force in the province, winning the most seats in the 1919 provincial election and forming a governing coalition with the Independent Labour Party. The UFO and its companion organizations, the United Farmers Cooperative Company (UFCC) and the United Farm Women of Ontario (UFWO), flourished, achieving much of its success by challenging those who controlled the economic, political, and social structures in Ontario and advancing an alternative vision of democracy that sought to maximize citizen participation in the decision-making process. By the mid-1920s the UFO had gone into a period of decline from which it never recovered. The promise of equality hoped for by UFWO members never materialized and the UFCC, once a key component in the development of an alternative vision, began to focus more on profits than on politics. In Ringing in the Common Love of Good Kerry Badgley explores both the rise and the fall of the UFO, focusing on the Ontario counties of Lambton, Simcoe, and Lanark. He challenges the liberal-capitalist interpretation that the movement was nothing more than a group of impatient Liberals, as well as the Marxist view that the UFO consisted of self-interested independent commodity producers. Badgley argues that as the UFO broke free from hegemonic forces it developed alternative economic, political, and social visions, but that it was these same forces, combined with internal struggles and a conservative leadership, that ultimately resulted in the decline of the movement as a vehicle for democratic change in Ontario. --Publisher's description

Employment Equity Policy in Canada: An Interprovincial Comparison - Bakan, Abigail B.; Kobayashi, Audrey Lynn (Status of Women Canada, 2000)
Keywords: Canada; Discrimination in employment; Employment Government policy; Government policy; Minority women

A Square Deal for All: Historical Essays on Labour in Brandon - Black, Errol; Mitchell, Tom (Canadian Committee on Labour History, 2000)
The authors' careful analyses of labour and working-class organizations in Brandon [Manitoba] are aimed at reconstructing and disclosing aspects of the history of class and class relations. While other western Canadian cities, Winnipeg, for example, have received much deserved attention by historians, studies of other cities, such as Brandon, in the early 20th century help to provide a more well-rounded understanding of working-class life in Canada during this period. In the tradition of the new labour history Black and Mitchell pay close attention to the unique development of class relations in the community of Brandon, while placing that community in a broader, national context. This work includes a careful consideration of the working class in Brandon, the particular obstacles and challenges workers there faced, and makes an important contribution to our understanding of class relations in Canada. --Publisher's description
Keywords: History; Labor; Labor Manitoba Brandon History; Labor movement; Labor movement Manitoba Brandon History; Manitoba Brandon; Mouvement ouvrier Manitoba Brandon Histoire; Travail Manitoba Brandon Histoire; Travailleurs Manitoba Brandon Histoire; Working class; Working class Manitoba Brandon History

English Immigrant Voices: Labourers' Letters from Upper Canada in the 1830s - Cameron, Wendy; Maude, Mary McDougall; Haines, Sheila (McGill-Queen's University Press, 2000)
Emigrants sent by the Petworth Emigration Committee were part of a wave of rural workers in the 1830s whose immigration to Upper Canada was sponsored by English parishes and landlords. Their letters written or dictated to family and friends, leave us a rare first-hand view of the immigrant experience from a working-class perspective. Collected from published, archival, and private sources, these letters place the Petworth immigrants in the context of their times and challenge the image of English immigrants to 1830s Upper Canada as officers and gentlewomen. Wendy Cameron, Sheila Haines, and Mary McDougall Maude have carefully annotated the letters to sketch the stories of individual writers, link letters by the same author or members of the same family, and explore the connections between writers. What eventually happened to some of the writers is also revealed in this engaging collection. English Immigrant Voices provides a valuable insight into the rural poor and their experiences in emigrating to a new land. --Publisher's description
Keywords: 19th century; British; Correspondence; History; Immigrants; Ontario; Working class

Canadian Marxists and the Search for a Third Way - Campbell, J. Peter (McGill-Queen's University Press, 2000)
The triumphs and failures of four Canadian Marxists who advocated organization and education rather than armed struggle in the revolutionary overthrow of capitalism and the creation of socialism. Literature on Marxist socialists in Canada has usually been written by those within the social democratic or Marxist-Leninist traditions and has generally failed to break free of the political biases of the defenders of these traditions. Canadian Marxists and the Search for a Third Way steps outside these approaches to appraise early Canadian Marxists on their own terms. Peter Campbell argues that their Marxism was a changing and evolving product of their intellectual development and day-to-day interaction with the Canadian working class. It was a dynamic, theoretical system that provided a "third way" to look at Marxism, a revolutionary socialism that rejected violence in favour of the broadest organization and education of the working-class majority. Focusing on four individuals, Canadian Marxists and the Search for a Third Way describes the lives and ideas of Ernest Winch, Bill Pritchard, Bob Russell, and Arthur Mould and examines their efforts to put their ideas into practice. Campbell begins by looking at their childhoods in Great Britain, particularly their religious upbringing. He considers their family life, their attitudes toward women and ethnic minorities, what they were reading, and what effect that reading had on their theory and practice. He describes their lives as labor leaders and advocates of socialism, revealing how tenaciously, in an increasingly hierarchical, bureaucratized, and state-driven capitalist society, they held to the idea that socialism must be created by the working class itself. This is a unique look at four Canadian Marxists and their struggle to create an educated, disciplined, democratic, mass-based movement for revolutionary change. --Publisher's description

Click, Clack, Moo: Cows That Type - Cronin, Doreen; Lewin, Betsy (Simon & Schuster Books for Young Readers, 2000)
Farmer Brown has a problem. His cows like to type. All day long he hears Click, clack, MOO. Click, clack, MOO. Clickety, clack, MOO. But Farmer Brown's problems REALLY begin when his cows start leaving him notes.... Doreen Cronin's understated text and Betsy Lewin's expressive illustrations make the most of this hilarious situation. Come join the fun as a bunch of literate cows turn Farmer Brown's farm upside down. --Publisher's description
Keywords: Cows; Domestic animals; Fiction; Typewriters

No Logo: Taking Aim at the Brand Bullies - Klein, Naomi (Flamingo, 2000)
The hotly debated report from the frontlines of mounting backlash against multinational corporations. A national bestseller, No Logo took Canadians by storm when it was published last year in hardcover. Equal parts cultural analysis, political manifesto, mall-rat memoir, and journalistic exposé, it is the first book to uncover a betrayal of the central promises of the information age: choice, interactivity, and increased freedom. No Logo takes apart our packaged and branded world and puts the pieces into clear pop-historical and economic perspective. Naomi Klein tracks the resistance and self-determination mounting in the face of our new branded world and explains why some of the most revered brands in the world are finding themselves on the wrong end of a bottle of spray paint, a computer hack, or an international anti-corporate campaign. --Publisher's description, Vintage edition
Keywords: Anti-Corporation; Brands; Corporate power; Multinational Corporations; Retail

Les relations du travail au Québec - Leclerc, Michel; Quimper, Michel (Presses de l'Université du Québec, 2000)
Les auteurs décrivent les aspects historiques, légaux et sociaux du Québec et les comparent avec ceux qui prévalent ailleurs. Ils brossent un tableau de la législation du travail, de la vie syndicale, de la négociation collective, de la gestion de la convention collective et de l'avenir des relations du travail. --Publisher's description
Keywords: Collective bargaining; Collective bargaining Québec (Province); Droit du travail; Employee-management relations in government; Employee-management relations in government Québec (Province); Industrial relations; Industrial relations Québec (Province); Labor laws and legislation; Labor laws and legislation Québec (Province); Labor unions; Labor unions Québec (Province); Livres électronique; Législation; Négociation collective; Négociations collectives Québec (Province); Personnel Direction Québec (Province); Personnel management; Personnel management Québec (Province); Québec; Québec (Province); Relations de travail; Relations industrielles Québec (Province); Secteur public; Secteurs public et para-public Relations de travail Québec (Province); Syndicat; Syndicats Québec (Province); Travail Droit Québec (Province)

Men for the Mountains - Marty, Sid (Penguin Random House Canada, 2000)
As a park warden in the national parks of Canada's Rocky Mountains, Sid Marty came to know that beautiful and treacherous landscape as few men or women do. He was a mountain climber, rescue team member, firefighter, wildlife custodian, and adviser to tourists, adventurers, and people passing through. At all times, he was an acute observer of human and animal behaviour. In these pages he records with wry wit and bitter insight true stories of heroism and folly drawn from life in the high country. Marty writes vividly about a land and a way of life that are increasingly endangered. The visceral energy of his prose compels attention. This is a compulsive, alarming, and often hilarious read. --Publisher's description
Keywords: Adventure; Fire Fighter; Humour; Landscape; Mountains; Rescue Team Member; Working with the land

Boys in the Pits: Child Labour in Coal Mines - McIntosh, R. G. (Robert G.) (McGill-Queen's University Press, 2000)
A controversial and chilling examination of child labour in Canadian coal mines, Boys in the Pit shows that beginning early in the nineteenth century, thousands of boys, some as young as eight, laboured underground - driving pit ponies, manipulating ventilation doors, and helping miners cut and load the coal that fuelled the industrial revolution. Boys died in the mines in explosions and accidents but they also organized strikes for better working conditions. Robert McIntosh recasts these wage-earning children as more than victims, illustrating that they responded intelligently and resourcefully to their circumstances. Boys in the Pits is particularly timely as, despite the United Nations Convention on the Rights of the Child, accepted by the General assembly in 1989, child labour still occurs throughout the world and continues to generate controversy. McIntosh provides an important new perspective from which to consider these debates, reorienting our approach to child labour, explaining rather than condemning the practice. Within the broader social context of the period, where the place of children was being redefined as - and limited to - the home, school, and playground, he examines the role of changing technologies, alternative sources of unskilled labour, new divisions of labour, changes in the family economy, and legislation to explore the changing extent of child labour in the mines. --Publisher's description
Keywords: Child labor; Coal miners

Who has Seen the Wind - Mitchell, W. O. (William Ormond) (McClelland & Stewart, 2000)
When W.O. Mitchell died in 1998 he was described as “Canada's best-loved writer.” Every commentator agreed that his best – and his best-loved – book was Who Has Seen the Wind. Since it was first published in 1947, this book has sold almost a million copies in Canada. As we enter the world of four-year-old Brian O’Connal, his father the druggist, his Uncle Sean, his mother, and his formidable Scotch grandmother (“she belshes…a lot”), it soon becomes clear that this is no ordinary book. As we watch Brian grow up, the prairie and its surprising inhabitants like the Ben and Saint Sammy – and the rich variety of small-town characters – become unforgettable. This book will be a delightful surprise for all those who are aware of it, but have never quite got around to reading it, till now. --Publisher's description
Keywords: Drugs; Prairies; Social Class and Equality

The IWA in Canada: The Life and Times of an Industrial Union - Neufeld, Andrew; Parnaby, Andrew (IWA Canada/New Star Books, 2000)
The IWA, while closely linked to BC, has played a crucial role in nearly every province in Canada, from the Queen Charlotte Islands to Grand Falls, Newfoundland. The IWA in Canada is a definitive history of the union that follows its progress and setbacks throughout the past century. Its predecessors, the Industrial Workers of the World, the One Big Union, and the Lumber Workers' Industrial Union are examined, as are the historical tensions between craft and industrial unionism, the drive to organize the "timber beasts", and the pioneering role of communist activists. Today, the legendary militancy of IWA members is being brought to bear on the legalistic negotiations, environmental movements, and evolutions in governmental forest policy that continue to pose challenges. Generously illustrated with historical and present?day photographs, and enriched by numerous interviews with founding unionists, The IWA In Canada also features capsule histories of each local. In-depth analysis of specific issues and events such as the mysterious death of Viljo Rosval and Jon Voutilainen, the fight for relief in the Great Depression and the Loggers' Navy can be found in sidebars that enhance the text throughout. --Publisher's description.
Keywords: Canada; History. Lumbermen; IWA Canada; International Woodworkers of America-Canada; Labor Unions; Labor unions. Woodworkers; Woodworkers

Labouring the Canadian Millennium: Writings on Work and Workers, History, and Historiography - Palmer, Bryan D. (Past CCLH Publications, 2000)
As Canadian workers, the labour movement, and scholars confront a new millennium, new opportunities and new challenges loom large. This volume, which mirrors Labour/Le Travail Volume 46, commissions a number of articles addressing themes that will be of consequence as we enter the 21st century. The articles that appear in this collection are authored by some of the more prominent social scientists working in the field of labour-related studies, among them Desmond Morton, Ian McKay, Joan Sangster, Cynthia Comacchio, David Frank, and Jacques Rouillard. Their writing appears in the book, grouped in a series of thematic sections: institutions and ideas; gender, sexuality and family; Quebec and the national question; culture; and workers and the state. Topics such as Canadian socialism, pivotal events such as the 1949 Asbestos strike, and important cultural undertakings, such as working-class representations on film and video, are addressed. Historiographical controversies and debates associated with the relations of women’s and working-class histories or different generational styles associated with the presentation of labour’s past are surveyed. This is an issue all interested in Canadian society and its development will not want to miss. --Publisher's description
Keywords: Canada; History; History. Labor movement; History. Working class; Labor; Labor movement; Working class

A Memoir of the Spanish Civil War: An Armenian-Canadian in the Lincoln Battalion - Stephens, D. P. (Douglas Patrick) (Past CCLH Publications, 2000)
A Memoir of the Spanish Civil War is one man's bittersweet account of fighting with the International Brigades against the forces of General Francisco Franco in Spain from 1936 to 1939. Douglas Patrick (Pat) Stephens was born in Armenia in 1910 and emigrated with his family to Canada in 1926. Like countless others, his dream of finding a new and more prosperous life was severely shaken by the onset of the Great Depression, and he turned to the Communist Party of Canada in an attempt to combat the political and economic deterioration which had gripped much of the world. Franco's attempt to overthrow by military force the republican government of Spain seemed to Pat Stephens the ideal opportunity to put his political convictions into action. Through his connections in the Communist Party, he became one of some 1400 Canadians, and 40,000 International Volunteers in all, who went to Spain. Many of the volunteers, including the Canadians, went to Spain against the laws and the wishes of their governments. Many of them never came back. Stephens' memoir, dictated to his wife Phyllis Stephens shortly before his death in 1987, puts a very human face on this strange and complex war. It is a portrait of political and moral conviction tinged by creeping disillusionment. It is also a compelling depiction of the strength, frailty, doubt, and courage which can result from the sometimes incongruous intersection of the personal and the political. A Memoir of the Spanish Civil War is a valuable contribution to our understanding of the conflict which immediately preceded World War II, and of Canada's role in that conflict. -- Publisher's description
Keywords: Civil War, 1936-1939; Ejército Popular de la República. Abraham Lincoln Battalion; History; Personal narratives, Canadian; Soldiers; Spain

Temporary Work: The Gendered Rise of a Precarious Employment Relationship - Vosko, Leah F. (Studies in comparative political economy and public policy, 2000)
The first in-depth analysis of temporary work in Canada, this book by Leah F. Vosko examines a number of trends, including the commodification of labour power; the decline of the full-time, full-year job as a norm; and the gendered character of prevailing employment relationships. Spanning the period from the late nineteenth to the late twentieth century, Temporary Work traces the evolution of the temporary employment relationship in Canada and places it in an international context. It explores how, and to what extent, temporary work is becoming the norm for a diverse group of workers in the labour market, taking gender as the central lens of analysis." "Recent scholarship emphasizes that the nature of work is changing, citing the spread of non-standard forms of employment and the rise in women's participation in the labour force. Vosko confirms that important changes are indeed taking place in the labour market, but argues that these changes are best understood in historical, economic, and political context. This book will be invaluable to academics in a variety of disciplines as well as to policy analysts and practitioners in government, industry, and organized labour. --Publisher's descsription
Keywords: 1900-1999; Canada; Canadá; Convenio de la OIT; Division sexuelle du travail Canada Histoire 20e siècle; Estados Unidos; Etats-Unis; Femmes Travail Canada Histoire 20e siècle; History; ILO Convention; ILO Recommendation; Recomendación de la OIT; Sexual division of labor; Sexual division of labor Canada History 20th century; Temporary employment; Temporary employment Canada History 20th century; Travail temporaire Canada Histoire 20e siècle; USA; Women Employment; Women Employment Canada History 20th century; agence de travail temporaire; agence pour l'emploi privée; agencia de empleo privada; collective bargaining; comentario; comment; commentaire; condiciones de empleo; conditions d'emploi; conditions of employment; contrat de travail; contratación; contrato de trabajo; convention de l'OIT; cuadros estadísticos; developed countries; discriminación por razones de sexo; discrimination fondée sur le sexe; division du travail basée sur le sexe; división del trabajo por sexo; domestic worker; empleo temporal; emploi temporaire; employment security; employé de maison; empresa de trabajo temporal; femmes mariées; flexibilidad del trabajo; flexibilité du travail; formación; formation; histoire; historia; history; immigrant; inmigrante; labour contract; labour flexibility; labour force participation; labour legislation; legislación del trabajo; législation du travail; married women; migrant workers; mujeres casadas; negociación colectiva; négociation collective; papel de la OIT; pays développés; países desarrollados; private employment agency; protección social; protection sociale; recommandation de l'OIT; recruitment; recrutement; role of ILO; rôle de l'OIT; salaire; salario; seguridad en el empleo; sex discrimination; sexual division of labour; sindicalización; social protection; statistical table; syndicalisation; sécurité de l'emploi; tableau statistique; tasa de actividad de mano de obra; taux d'activité; temporary employment; temporary work agency; tendance; tendencia; trabajador doméstico; trabajador migrante; trabajadoras; trade unionization; training